Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

A numerical solution of coupling hydro-mechanical behavior for subsea tunnels in strain-softening rock masses: theory and case study - Qingming Yan; Lan Cui; Youkou Dong; Qian Sheng; Biting Xie (European Journal of Environmental and Civil Engineering, 2026)

Geostationary observations of air pollutants from biomass burning: A synergy of GIIRS and GEMS over Southeast Asia - Shan Han; Shangyi Liu; Mengya Sheng; Jhoon Kim; Ximin Cui; Minqiang Zhou; Wei Wang; Isamu Morino; Voltaire A. Velazco; Zhao-Cheng Zeng (Remote Sensing of Environment, 2026)

Sepiolite-driven facet reconstruction of MOFs: Multi-pathway enhancement for ultrafast antibiotic degradation - Haishuai Cui; Sheng Jiang; Hailin Wang; Ying Lan; Yang Ma; Weijie Zhang; Huiyue Xin; Fuhua Huang; Huajie Liu; Hai Yang (Applied Clay Science, 2026)

Disguise strategy-adjusted controlled cleavage of DNA hydrogel for precision theranostics in colorectal cancer - Bo Han; Haitao Cui; Wenhui Chen; Zixiao Ma; Dandan Liang; Dongyang Wang; Jinghui Zhang; Juan Song; Sheng Tang (Chemical Engineering Journal, 2026)

Valorization of microalgal lipids for the production of high-value bio-based epoxidized monomers - Jiarong Tian; Siyuan Zhang; Yue Liu; Wei Rao; Kuichuan Sheng; Jun Wang; Yu Tang; Shaoqing Cui (Biomass and Bioenergy, 2026)

Dual-site magnetic microporous organic networks enabling high-performance capture and quantification of per- and polyfluoroalkyl substances - Chun-Ying Xu; Qing-Zhi Hou; Xiang-Sheng Xue; Zhan-Hui Qiu; Yuan-Yuan Cui; Cheng-Xiong Yang (Water Research, 2026)

Nonlinear permeability evolution in clay-rich fault zones under cyclic hydraulic gradients: Insights from in-situ experiments - Huimin Wang; Yuanyang Zhao; Junxian Lin; Anzhe Cui; Xiaohu Hu; Jinchang Sheng (Engineering Geology, 2026)

Thermodynamic and kinetic regulation of small-molecule acceptor via chlorinated thiophene side-chain engineering for as-cast toluene-processed organic solar cells - Jianlong Hu; Jianan Sheng; Hang Yang; Kewei Hu; Jiahao Qian; Xuncheng Zhu; Xiangyu Zheng; Tingting Fang; Yue Wu; Youkuo Wang; Chaohua Cui; Yongfang Li (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Mechanisms of midgut injury induced by chronic trace concentrations of chlorantraniliprole in silkworm (Bombyx mori) - Sheng Zhang; Jialu Cheng; Xueling Qin; Guimin Nong; Xiaoqing Cui; Zhaoshen Lu; Bing Li (Pesticide Biochemistry and Physiology, 2026)

Global prevalence and distribution of bla-harboring Salmonella: A genome-wide association study of cephalosporin resistance mechanisms - Qiuping Yang; Jingsen Zhang; Tianxi Chen; Min Li; Mei Li; Huanjing Sheng; Shenghui Cui; Baowei Yang (Food Microbiology, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Stochastic Seismic Fragility Analysis for Tunnel Linings with Rubber Concrete Under Near-Fault Ground Motions - Jiajun Wu; Xiancheng Mei; Hao Sheng; Zhen Cui; Qian Sheng; Jian Chen (Rock Mechanics and Rock Engineering, 2026)

Effects of ground motion types and rubber-sand-concrete damping layer on the seismic fragility of tunnel linings - Kaichen Li; Changdong Ding; Xiancheng Mei; Hao Sheng; Zhen Cui; Xuesong Cai; Jiajun Wu; Qian Sheng; Jian Chen (Transportation Geotechnics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Extreme heat reshapes urban green space vitality: Dynamic response typologies, nonlinear built-environment associations, and configuration patterns in Nanjing - Zhonghu Zhang; Yi Shi; Junyan Yang; Huaxing Sheng; Xun Zhang; Ao Cui; Zhihan Zhang; Daijun Chen; Haocheng Sun (Building and Environment, 2026)

Polycyclic aromatic hydrocarbons exposure and hyperuricemia: insights from China-Northern Anhui Coal workers Cohort study to network toxicology analysis - Xiang Zhang; Fengtao Cui; Wenrui Zhao; Tianhe Xia; Qingqing Yang; Sheng Wang; Qi Zhong; Chengfan Zhou; Xinping Ding; Jin Yang; Wei Gao; Tong Shen (Environmental Geochemistry and Health, 2026)

Fracture behavior and constitutive modeling of rock-concrete contact surfaces with different roughness under freeze–thaw cycles - Mengyuan Cui; Taoying Liu; Yeshan Sheng; Min Tang; Wenbin Cai; Longjun Dong (Bulletin of Engineering Geology and the Environment, 2026)

Establishment and Application of a Triple TaqMan qPCR Detection Method for IMNV, DIV1, and CMNV - Yuzhi Wang; Chuang Cui; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Fish Diseases, 2026)
The escalating incidence of emerging pathogens and their propensity for co‐infection pose a severe threat to the sustainable intensification of Penaeus vannamei aquaculture. To address this challenge, a novel triplex TaqMan quantitative PCR (qPCR) assay was developed for the simultaneous detection of three high‐risk agents: Infectious Myonecrosis Virus (IMNV), Decapod Iridescent Virus 1 (DIV1), and Covert Mortality Nodavirus (CMNV). This study not only establishes a robust multiplex platform but also systematically optimises its performance, achieving superior analytical sensitivity and reproducibility compared to existing single‐target or duplex methods. The assay demonstrated a limit of detection as low as 10 1 copies/μL for all targets, with excellent inter‐ and intra‐assay coefficients of variation (CVs) consistently below 3%. Notably, the method effectively overcomes the technical hurdles associated with detecting both RNA (IMNV, CMNV) and DNA (DIV1) viruses within a single reaction, eliminating cross‐reactivity and ensuring high specificity. Validated against clinical samples, the established protocol exhibits a concordance rate exceeding 95% with current standard methods, while significantly streamlining the diagnostic workflow. This advancement provides a powerful tool for routine biosecurity monitoring, seed stock certification, and the comprehensive management of emerging shrimp diseases.

External Water Pressure Assessment on Initial Support in Drill-and-Blast Subsea Tunnels: A Comprehensive Review - Sartaj Hussain; Javid Hussain; Sheng Qian; Lan Cui (Journal of Marine Science and Engineering, 2026)
Subsea tunnels constructed by the drill-and-blast method are increasingly required in modern infrastructure and are often exposed to high groundwater pressure and fractured rock conditions. In such environments, external water pressure acting on initial support strongly affects tunnel stability, durability, and construction safety. Because the initial support is temporary, discontinuous, and prone to cracking, evaluation of its water pressure response remains challenging. Current design practice relies on simplified assumptions and empirical approaches, inadequate for fractured rock masses under high water pressure. This review synthesizes research on external water pressure in tunnels, with emphasis on drill-and-blast subsea tunnels. Empirical reduction coefficient methods, theoretical analytical solutions, numerical techniques, and physical model testing are critically examined in terms of their theoretical basis, applicability, and limitations. Special attention is given to seepage behavior in fractured rock masses, including single-fracture seepage laws, equivalent continuum models, and discrete fracture network approaches, and their ability to represent fracture-controlled flow and water pressure redistribution. The review shows that conventional seepage or seepage–stress coupled methods are insufficient to capture stress redistribution, fracture evolution, and damage-induced permeability changes governing water pressure behavior. By contrast, advanced coupled stress–seepage–damage and stress–seepage–fracturing models provide more physically consistent frameworks for analyzing external water pressure acting on initial support. In addition, hydro-mechanical discrete lattice models are reviewed as a promising meso-scale framework for capturing crack initiation, crack coalescence, and crack-controlled seepage paths that may govern localized external water pressure redistribution behind initial support. However, their application to subsea tunnels remains limited, and current design codes still lack unified calculation methods. Major challenges remain, including the lack of consistent definitions of external water pressure, inadequate consideration of the interaction between tunnel support and surrounding rock, and insufficient validation through laboratory experiments and field observations. Future research should develop mechanism-based methods supported by monitoring and validation to improve subsea tunnel safety.

USV autonomous collision avoidance strategy via GMM-distributional soft actor-critic in complex maritime environments - Shuhui Hao; Wei Guan; Xianku Zhang; Zhewen Cui; Sheng Qu (Ocean Engineering, 2026)

Experimental study on dynamic response of a calcareous seabed around a trenched pipeline under non-linear wave–current loading - Zuodong Liang; Dajun Liu; Lin Cui; Mengxiao Li; Zheng Wang; Dayu Chang; Hailun Chen; Ke Sun; Jisheng Zhang; Dong-Sheng Jeng (Ocean Engineering, 2026)

Establishment of A triplex TaqMan qPCR assay for EHP, VpTPD, VpAHPND with optimized efficacy using methyl cellulose - Yuzhi Wang; Chuang Cui; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Invertebrate Pathology, 2026)

Quantitative Early Warning of Floor Water Inrush Based on Deep Learning: Joint Response of Microseismic Three-Dimensional Kernel Density and Hydrodynamics - Hang Li; Xianjie Hao; Jinyi Ji; Huaixiang Yang; Wantong Lin; Sheng Zhang; Xinlei Cui (Rock Mechanics and Rock Engineering, 2026)

Evaluation of landslide susceptibility in alpine canyon area based on random forest method: a case study of southeast Tibetan Plateau - Haoran Dong; Qing Yang; Chong Xu; Huiran Gao; Shuzhong Sheng; Yulong Cui; Saier Wu; Lei Li; Peng Wang; Jingjing Sun (Bulletin of Engineering Geology and the Environment, 2026)

A new fatty acid derivative derived from the deep-sea fungus Aspergillus sp. SCSIO41324 - Yu-Shi Chen; Ying-Ying Song; Sheng-Yi Deng; Xin-Kai Xiao; Xiao-Yan Pang; Wei-Jia Zhang; Yong-Hong Liu; Hong-Hua Cui; Jun-Feng Wang (Natural Product Research, 2026)

Triboelectric-based multiphysical energy-information perception for in-situ wind turbine blade health monitoring - Hengrui Sheng; Rongwei Huang; Jiaxin Hu; Yuejuan Li; Yanshuo Sun; Yusong Cui; Leo N.Y. Cao; Baodong Chen; Herbert E. Huppert; Zhaohui Yao; Zijie Xu; Zhong Lin Wang (Chemical Engineering Journal, 2026)

Organic-matter accumulation of Carboniferous-Permian coal measure strata, central Ordos Basin, China: controlled by the provenance, paleoenvironment, and paleoproductivity - Xinzhu Sheng; Shu Tao; Fan Yang; Yi Cui; Zhuoyuan Ma; Yijie Wen; Ding Song (Carbonates and Evaporites, 2026)

Quantum tunneling effects on hydrogen transport in lanthanum trihydrides - Chunlei Yang; Luhao Zhang; Cui Zhang; Qiuhao Xu; Qunfang Gu; Yunzhe Jia; Wei Fang; Sheng Meng; Enge Wang (Science Bulletin, 2026)

Bridging the gap between empirical and rational design: machine learning framework for lithium ion-sieve performance prediction - Zhenjie Cui; Sheng Pang; Xinying Ren; Jianwei Guo; Hong Yue; Dong Wang; Zhi Wang (Desalination, 2026)

Zircon evidence for exogenous water delivery to the lunar interior - Yong Wang; Xiao-Ping Xia; Jian Xu; Yong-Sheng Liu; Christopher J. Spencer; Trevor Ireland; Ze-Xian Cui; Xiao-Jia Zeng; Jan C.M. De Hoog; Aaron J. Cavosie; Bin Fu; Qing Yang; et al. (Earth and Planetary Science Letters, 2026)

In situ formed biphasic high-entropy silicate ceramic aerogels reinforced by Al2O3 nanorods for high-temperature thermal insulation - Sisi Shang; Wenzhuo Hao; Zhen Zhang; Cheng Zhou; Jian Yang; Sam Sukgoo Yoon; Sheng Cui (Chemical Engineering Journal, 2026)

Heterogeneous agent proximal policy optimization for UAVs-USV formation navigation with multi-modal perception - Zhewen Cui; Wei Guan; Shuhui Hao; Tongbo Hu; Sheng Qu; Xianku Zhang (Ocean Engineering, 2026)

Disturbance rejection control Strategy of Stewart-gangway hybrid system for active wave compensation - Xiaokai Cui; Wenxuan Wang; Sheng Gao; Peng Xu; Bing Li (Ocean Engineering, 2026)

Water-level drives DOM-microbe interactions and carbon–nitrogen cycling in a large reservoir ecosystem - Qiaoqiao Li; Hua Ma; Hai Huang; Mingxing Cao; Yixuan Ye; Sheng-Ao Li; Yuhan Jiang; Zhe Li; Guowei Li; Fuyi Cui (Journal of Hydrology, 2026)

Environmental benzophenone exposure promotes breast cancer cell metastasis via the Wnt/β-catenin pathway - Jinlan Wei; Yanxia Hu; Chenxu Wang; Yu Deng; Liwei Chen; Fengzhen Cui; Yuanyuan Li; Xia Sheng (Journal of Hazardous Materials, 2026)

In Situ small-angle X-ray scattering study of the gelatinization mechanism of maize starches with varying amylose content - Ying Cui; Xiaoning Liu; Qi Lv; Jinhui Chang; Andreas Blennow; Yu Tian; Sheng Chen; Xingxun Liu; Yuyue Zhong (Food Hydrocolloids, 2026)

Experimental Study of the Combined Action of Random Waves and Current Induced Hydrodynamics and Seabed Response Around a Protective Three-Dimensional Pipeline - Dayu Chang; Risheng Wang; Wenqi Si; Mengxiao Li; Zheng Wang; Dajun Liu; Ke Sun; Dong-Sheng Jeng; Lin Cui; Dejian Wei (Journal of Marine Science and Engineering, 2026)
Submarine pipelines serve as the primary transportation infrastructure for offshore energy resources and are becoming increasingly important in modern industrial and domestic applications. A series of laboratory experiments on the dynamic seabed response of three-dimensional pipeline-seabed systems under random wave and current conditions was conducted. The results demonstrate as follows: (1) Under the combined action of random waves and ambient currents, the wave profiles in the vicinity of the submarine pipeline exhibit distinct irregular and nonlinear characteristics; (2) Compared with random waves acting alone, the superposition of random waves and currents modifies wave propagation behavior: a co-directional current enhances wave propagation, whereas a countercurrent suppresses it; (3) For a pipeline subjected to the three-dimensional random waves, pore-pressure amplitude decreases with increasing wave-incidence angle. Specifically, maximum values corresponding to incidence angles of 30° and 45° are generally lower than those at 0° and 15°, at a seabed depth of z/d = 0.0938, and the value at an incident angle of 45 degrees attenuates by 21.31% compared to that of 0°; (4) Coarse sand exhibits weaker pore-pressure attenuation than fine sand around the three-dimensional pipeline-seabed scheme, indicating that sediment grain size exerts a substantial influence on seabed response; (5) The protective effect of geotextile and stone is more obvious, whereas PVC is limited to the front and underside of the pipe. The deeper the seabed, the smaller the effect of protective measures. For reproducibility, the test matrix covered wave-incidence angles α = 0°, 15°, 30°, and 45°, irregular-wave conditions with H1/3 = 0.08–0.14 m and T1/3 = 1.2–1.8 s, and currents U = –0.2 m/s at a constant still-water depth h = 0.45 m.

SEAF-Net: A Sustainable and Lightweight Attention-Enhanced Detection Network for Underwater Fish Species Recognition - Yu-Shan Han; Sheng-Lun Zhao; Chu Chen; Kangning Cui; Pingfan Hu; Rui-Feng Wang (Journal of Marine Science and Engineering, 2026)
This study presents SEAF-Net, a lightweight and efficient detection network designed for low-contrast and highly dynamic underwater environments. Built upon YOLOv11n, SEAF-Net introduces three complementary structural enhancements: (1) Omni-Dimensional Dynamic Convolution (ODConv) to improve adaptive modeling of multi-scale and directional texture variations; (2) SimA-SPPF, which embeds the SimAM attention mechanism into the SPPF module to enable neuron-level saliency reweighting and effective suppression of complex background interference; and (3) GhostC3k2 to reduce redundant computation while preserving sufficient representational capacity. Evaluated on a standardized 13-class underwater fish dataset under a unified training and evaluation protocol, SEAF-Net achieves 6.1 GFLOPs, 92.683% Precision, 88.459% Recall, 93.333% mAP50, 73.445% mAP, and a 90.522% F1-score. Compared with the YOLOv11n baseline, SEAF-Net improves F1-score and Recall by 0.510% and 0.575%, respectively, while reducing computational cost by approximately 6%, demonstrating a favorable accuracy–efficiency trade-off under lightweight constraints. Ablation results further confirm that SimA-SPPF plays a dominant role in background suppression, ODConv consistently enhances deformation and directional texture modeling, and GhostC3k2 effectively controls computational overhead without degrading detection accuracy. To assess deployment feasibility, additional test set evaluations were conducted under deployment-oriented conditions using resource-limited hardware, yielding an F1-score of 88.54%. This result confirms that the proposed model maintains stable detection performance and robustness beyond training and validation stages. Overall, SEAF-Net provides an effective balance of accuracy, efficiency, and robustness, offering practical support for low-carbon, scalable, and sustainable intelligent aquaculture monitoring and underwater ecological assessment in real-world environments.

Experimental study on the resetting of IRSL and IRPL signals induced by frictional heating in rocks at seismic slip velocities - Furong Cui; Huili Yang; Jie Chen; Lu Yao; Jinfeng Liu; Jintang Qin; Myungho Kook; Sheng-Hua Li (Quaternary Geochronology, 2026)

Molecularly engineered interfaces drive nano-entanglement architectures for synergistic mechanical amplification in silicone rubber composites - Longjin Huang; Xiaomin Song; Yang Yang; Zihao Song; Sisi Shang; Zheyu Yang; Zihan Wang; Ping Zhang; Shichun Li; Xueyan Zhao; Sheng Cui; Chunhua Zhu; et al. (Chemical Engineering Journal, 2026)

Integrated Rock Physics-Based Interpretation of Time-Lapse Seismic Data for Residual Oil Detection in Offshore Waterflooded Reservoirs - Haoyuan Li; Xuri Huang; Sheng Yang; Xiaoqing Cui; Yibin Li; Ran Yang (Journal of Marine Science and Engineering, 2026)
Accurate characterization of fluid distribution in offshore waterflooded oilfields has been challenging due to complex heterogeneity and the limitations of traditional interpretation tools, which often cannot integrate multi-scale datasets such as core samples, well logs, and seismic surveys. This study addresses these challenges by developing an integrated interpretation workflow based on a calibrated rock physical fluid substitution model. The model, constrained by low-frequency laboratory measurements and elastic parameters from well logs, is used to assess the impact of fluid variations on core elastic properties and to ensure physical consistency across core, log, and seismic data scales. Key findings demonstrate that the calibrated model effectively detects impedance changes caused by water injection and accurately identifies remaining oil deposits. When applied to time-lapse seismic interpretation and reservoir numerical simulation, the model proves valuable for guiding infill well placement and optimizing development strategies in mature offshore reservoirs. Additionally, this approach provides a robust framework for integrating multi-source data, thereby enhancing the reliability of reservoir characterization in waterflooded wells.

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

An improved ISPH model for simulating wave–current interactions and turbulence evolution over submerged reefs - Dong Wang; Haopeng Wang; Sheng Yan; Jianguo Lin; Jiawen Sun; Jingdan Cui; Junyi Xi; Tao Liu (Ocean Engineering, 2026)

Ion-mediated interfacial water reconstruction in cellulose-biochar aerogels enables seawater evaporation faster than pure water - Man Yuan; Lei Yang; Wei Liu; Meng Hu; Cheng Zhou; Xiaobei Guo; Sheng Cui (Chemical Engineering Journal, 2026)

Engineering of β-glucosidase CaBGL with improved performance in cellulose hydrolysis - Cai You; Xin Zheng; Kuan Qi; Sheng Dong; Ya-Jun Liu; Chao Chen; Qiu Cui; Yingang Feng (Bioresource Technology, 2026)

MCM3 Safeguards Neural Progenitor Maintenance and Cortical Development Against Replication-Associated Stress - Zhenyan Xu; Jing Chen; Sheng He; Yongshan Gao; Yangyang Li; Yu Guo; Ling Yan; Caiyun Ma; Xiaoling Cui; Wensheng Jiang; Changqing Liu; Yixiang Xing; et al. (Molecular Neurobiology, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Shuyu capsule improves estrous cycle-dependent depression-like behavior in premenstrual dysphoric disorder (PMDD) mice by increasing GABAergic neuronal activation and downregulating GABAAR δ subunit expression in the dorsal periaqueductal gray (dPAG) region - Jialing Xu; Kun Liu; Yaru Cui; Hao Zhang; Xinyu Wang; Minghui Hu; Zifa Li; Peng Gao; Wei Liu; Mingqi Qiao; Wenqiang Cui; Xiwen Geng; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The collaborative navigation decision-making method of USV by UAV based on improved PPO algorithm - Sheng Qu; Wei Guan; Tongbo Hu; Zhewen Cui (Ocean Engineering, 2025)

Programmable manganese-chalcogen coordination nanoregulator enables dual-lock prodrug activation through electron cloud engineering for synergistic chemo-metalloimmunotherapy - Jingzhe Sheng; Tengda Du; Jingyi Zhang; Yuetong Huang; Shuo Wang; Mengyu Liu; Tao Zhang; YingJie Zhao; Hao Zhang; Qian Lv; Can Zhao; Xiaoxue He; et al. (Chemical Engineering Journal, 2025)

Novel thermal-insulating and microwave-absorbing AlN/C aerogels prepared via solvent-free ambient pressure aging combined with carbothermal reduction nitridation technique - Qi You; Fuhao Xu; Ya Zhong; Sheng Cui (Chemical Engineering Journal, 2025)

Identification of writers and erasers in tomato and their response to drought stress and hormones - Yushi Lu; Sheng Luo; Jing Cui; Yuxia Yao; Yuna Pan; Wenjin Yu; Changxia Li (Plant Cell Reports, 2025)

Production of Fc-fused receptor agonists for glucagon-like peptide-1/glucose-dependent insulinotropic polypeptide (GLP-1/GIP) in the milk of transgenic mice - Yu Rao; Shuai Yu; Bao-Zhu Wang; Sheng Cui; Ke-Mian Gou (Transgenic Research, 2025)

Deep learning-based inversion of stress curves and crack quantification in NPR anchored rock masses - Li Cui; Wenfeng Ren; Chengyu Miao; Yong Zhang; Chengwei Zhao; Sheng-tian Zhai; Ran Hai; Jianjun Ma; Xiaoming Sun (Journal of Mountain Science, 2025)

Marine antifouling coating based on modified polyurethane and halloweite nanotubes for slow-release of chlorgentianol alcohol - Yuan Feng; Chi Zhang; Yong-Yin Cui; Miao-Qing Sheng; Xian-Dong Zhang; Hui-Jing Li; Yan-Chao Wu (Applied Clay Science, 2025)

Experimental Study on Seabed Stability Around an Offshore Pipeline Under Waves and Currents: Local Scour and Pore-Water Pressure - Mengxiao Li; Dong-Sheng Jeng; Lin Cui; Zuodong Liang; Zheng Wang; Dajun Liu; Dayu Chang; Ke Sun (Journal of Marine Science and Engineering, 2025)
Offshore pipelines are commonly used for the transportation of oil and gas from offshore to near-shore facilities in the oil and gas industry. In ocean environments, the wave- and current- induced pore-water pressure within the seabed, and the associated seabed liquefaction and local scour around pipelines, are widely recognised as among the key factors in the design of offshore pipelines. In this paper, a series of wave flume experiments were carried out on the three-dimensional (3D) scouring around a pipeline. In the experiment, in addition to the measurement of hydrodynamic characteristics and local scour, the pore-water pressure within a sandy seabed was measured. Both waves and currents were considered with different incident angles to the pipeline. This study focuses on the relationship between the variation in pore-water pressure and the development of the scouring process around the pipeline, as well as the evolution of the 3D scouring morphology near the pipeline. The experimental results show that the pore-water pressure exhibits significant changes (up to 12.5% of P0) in the beginning stage of the scouring process, especially in the area below the pipeline, where the influence of scouring on pore-water pressure is most obvious.

Numerical Analysis of a Vertical Axis Wind Turbine with Racetrack Trajectory - Sixiong Ge; Yan Yan; Zhecheng Lou; Jie Xu; Zhehao Sheng; Jiahuan Cui (Journal of Marine Science and Engineering, 2025)
This study presents a comprehensive numerical and theoretical analysis comparing the aerodynamic performance of a racetrack trajectory vertical axis wind turbine with a baseline VAWT. The racetrack trajectory comprises two parallel straight segments connected by semicircular arcs. However, two critical research gaps remain: the aerodynamic performance of this non-axisymmetric rotor, especially its sensitivity to inflow direction, is not well understood, and a computationally efficient theoretical model for its rapid design is lacking. Using unsteady Reynolds-Averaged Navier–Stokes (URANS) simulations to systematically quantify this sensitivity, and developing an adapted double multiple streamtube (DMST) model, the performance of both turbines is evaluated across tip speed ratios (TSRs) of 1.5–4 and inflow angles β = 0–90°. Results indicate that the racetrack turbine achieves a peak power coefficient of 0.49 at TSR = 2.5 and β = 90°, 16.7% higher than the baseline VAWT. Its performance is highly sensitive to inflow direction, whereas the baseline operates more uniformly across angles. Flow field and wake analyses reveal that the racetrack turbine exhibits faster wake recovery and lower turbulence intensity downstream under optimal inflow. This study demonstrates the potential of racetrack turbines for enhanced directional efficiency in marine wind conditions and validates the adapted DMST model as a reliable tool for preliminary design.

The response characteristics of fault-crossing tunnel subjected to different sequential combination actions of strike-slip fault dislocation and seismic wave propagation - Xiancheng Mei; Changdong Ding; Jianhe Li; Bo Lou; Zhen Cui; Mingnan Xu; Qian Sheng; Yajie Song; Jian Chen (Soil Dynamics and Earthquake Engineering, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Microbial community dynamics and ecological interactions during an atypical winter Cerataulina pelagica (Bacillariophyta) bloom in Laizhou Bay, southern Bohai Sea - Long Yang; Hongwei Wang; Zhengguo Cui; Hualong Wang; Xiaokun Ding; Di Zhang; Huanyu Zhang; Sheng Li; Tao Jiang (Marine Environmental Research, 2025)

Regulatory mechanisms of carboxylic ligands with varying carboxyl group richness in Fe(II)-catalyzed ferrihydrite transformation - Yuefei Ding; Anxu Sheng; Jiahao Chen; Yurong Deng; Xinglan Cui; Juan Liu (Geochimica et Cosmochimica Acta, 2025)

Safety and recyclability of active polyethylene terephthalate bottles: A comprehensive assessment using non-target screening and visual sensory evaluation - Can Xu; Sheng Chen; Qi-zhi Su; Jinxin Liang; Ying Zeng; Anqi Cui; Hanke Li; Ben Dong; Dan Li; Huai-ning Zhong (Food Chemistry, 2025)

The synergistic effect of double catalysis of TGase-mediated limited deamidation and cross-linking of zein to form multifunctional zein-based film for food preservation - Na Li; Yutong Sheng; Sihan Liao; Jingwen Zhang; Ying Liu; Ping Wang; Li Cui (Food Chemistry, 2025)

Greenhouse gas emissions in a microbial fuel cell-assisted composting system: Microbial insights into bacterial structures and genetic functions - Hu Cui; Sheng-Nan Hou; Xin-Yi Wang; Hui Zhu (Environmental Research, 2025)

Universal ionic wind tweezer for non-contact, phase-inclusive micromanipulation - Qiang Tang; Chengcheng Song; Manfei Liu; Xiaxia Cui; Junjie Zhang; Zetao Wang; Sheng Zhang (Chemical Engineering Journal, 2025)

Synthesis of LaAlO3 based high near-infrared reflective red pigment by substituting A-site and B-site elements in perovskite structure with Ca2+/Cr3+ - Qiuli Fang; Jingsheng Liu; Yi Wu; Kangzhen Sun; Pengzhai Li; Cheng Cai; Sheng Cui; Yin Zhang (Chemical Engineering Journal, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Dual-catalytic polymerization of high-performance PEDOT thermoelectric fabrics for self-powered sensing - Yifan Cui; Qin Chen; Wuwei Bao; Hao Yao; Zhenzhe Huang; Rui Ma; Miao Miao; Lizhi Sheng; Xinyang He (Chemical Engineering Journal, 2025)

Solvent-polarity-engineered hyaluronic acid aerogels: Synthesis of transparent nanofiber network for thermal insulation - Yufang Lu; Shanying Sui; Miao Cui; Jingxing Wang; Yufan Yang; Yuhan Sheng; Yi Zhang; Zhifang Sun (Carbohydrate Polymers, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Research on Collision Avoidance Method of USV Based on UAV Visual Assistance - Tongbo Hu; Wei Guan; Chunqi Luo; Sheng Qu; Zhewen Cui; Shuhui Hao (Journal of Marine Science and Engineering, 2025)
Collision avoidance technology serves as a critical enabler for autonomous navigation of unmanned surface vehicles (USVs). To address the limitations of incomplete environmental perception and inefficient decision-making for collision avoidance in USVs, this paper proposes an autonomous collision avoidance method based on deep reinforcement learning. To overcome the restricted field of view of USV perception systems, visual assistance from an unmanned aerial vehicle (UAV) is introduced. Perception data acquired by the UAV are utilized to construct a high-dimensional state space that characterizes the distribution and motion trends of obstacles, while a low-dimensional state space is established using the USV’s own state information, together forming a hierarchical state space structure. Furthermore, to enhance navigation efficiency and mitigate the sparse-reward problem, this paper draws on the trajectory evaluation concept of the dynamic window approach (DWA) to design a set of process rewards. These are integrated with COLREGs-compliant rewards, collision penalties, and arrival rewards to construct a multi-dimensional reward function system. To validate the superiority of the proposed method, collision avoidance experiments are conducted across various scenarios. The results demonstrate that the proposed method enables USVs to achieve more efficient autonomous collision avoidance, indicating strong potential for engineering applications.

Spermidine-mediated enhancement of salt tolerance in cucumber and the role of H2O2 in regulating this enhancement - Ting-Ting Xu; Cui-Yun Dong; Cai-Hong Chai; Qiao Zhu; Cheng Ma; Zi-Qi Pei; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Biologia, 2025)

Understanding aerosol pollutant generation in wet-mix shotcrete for tunnel construction - Kun-Hua Liu; Shu Wang; Jia-Wei Zhao; Zhen Guo; Sheng-nan Ou; Long-Zhe Jin; Jun-yong Cui (Tunnelling and Underground Space Technology, 2025)

Application of hydrocolloids in the quality improvement of flour-based products - Xingmei Sheng; Qi Cui; Haotian Yin; Zijun Xi; Junjie Yi; Huang Zhang; Xueming Xu; Yongshuai Ma (Trends in Food Science & Technology, 2025)

The role of potassium in lode gold mineralization: insights from ab initio molecular dynamics and geochemical modeling - Gao-Hua Fan; Jian-Wei Li; Yuan Mei; Si-Yu Hu; Ri-Chen Zhong; Chang Yu; Xiao-Dong Deng; Hao Cui; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Dual-functional GO composite aerogels for water purification and desalination via heavy metal adsorption and solar evaporation - Man Yuan; Lei Yang; Zihan Wang; Jiangping Du; Sisi Shang; Wei Liu; Meng Hu; Sheng Cui (Desalination, 2025)

Synergistic Rb+-dual-network polymer gel electrolyte enhances stability of dendrite-free Zn2+ batteries - Xin Ye; Sisi Shang; Bo Zhao; Wei Liu; Suting Liu; Cunguo Wang; Sheng Cui; Hongqing Zhou (Chemical Engineering Journal, 2025)

Cement aerogel building envelopes: achieving building energy efficiency and acoustic noise reduction - Zihao Song; Haoran Ma; Man Yuan; Sisi Shang; Wei Liu; Sam Sukgoo Yoon; Sheng Cui (Chemical Engineering Journal, 2025)

Source resolution and model prediction of hydrogen peroxide produced through photochemistry and phytoplankton species in environmental waters - Zhe Li; Sheng-Ao Li; Hua Ma; Lianggen Ao; Guowei Li; Fuyi Cui (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Unified models for water permeability in hydrate-bearing sandy soil considering pore morphology evolution - Lin-Yong Cui; Chao Zhou; Sheng Dai (Geomechanics for Energy and the Environment, 2025)

Construction of protective layer on PET fabric by utilizing hydrophilic-hydrophobic interactions for sensing, flame retardancy and thermal management properties - Weiwen Gu; Jian Liu; Xiaowei Su; Peng Qi; Xinyu Cui; Yujia Wang; Hongfei Li; Xiaoyu Gu; Jinping Xiong; Jun Sun; Sheng Zhang (Chemical Engineering Journal, 2025)

Single-atom Fe-N4 sites on crumpled N-C-MoS2 nanospheres for peroxymonosulfate activation and FeIV=O generation - Yu Yin; Wenning Li; Xuan Li; Yantao Wang; Qinxin Wang; Abdul Hannan Asif; Sheng Cui; Xiaoguang Duan; Shaobin Wang; Hongqi Sun (Chemical Engineering Journal, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Efficient methane decomposition to produce hydrogen and microwave absorption material by iron and nitrogen Co-doped Biocarbon: Synergistic mechanisms and performance - Haipeng Cui; Song Hu; Tao Yang; Limo He; Kai Xu; Long Jiang; Sheng Su; Yi Wang; Jun Xu; Jun Xiang (Biomass and Bioenergy, 2025)

Emergence of multidrug resistance and genomic analysis of azithromycin-resistant non-typhoidal Salmonella from diverse sources in China, 2006–2018 - Qiuping Yang; Xiaoqi Wang; Li Su; Huanjing Sheng; Yuchen Jin; Wenjing Lu; Hongyang Zhao; Shenghui Cui; Baowei Yang (Veterinary Microbiology, 2025)

Neutral pH induces complex and stable soil microbial networks in agricultural ecosystems - Jianwei Zhang; Zhiying Guo; Jie Liu; Xianzhang Pan; Yanan Huang; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Jing Sheng (Plant and Soil, 2025)

Six Weeks of Moderate-Intensity Treadmill Exercise Improves Intestinal Barrier and Intestinal Inflammation in Parkinson’s Disease Mice - Ting Li; Sheng-Yang Zhou; Wei Quan; Yu Zhou; Jian Wu; Li-Ping Zhao; Chen-Meng Qiao; Wei-Jiang Zhao; Chun Cui; Yan-Qin Shen (Molecular Neurobiology, 2025)

Effects of Simulated Acid Rain Aging on the Bioavailability of Cadmium in Contaminated Soil Amended with Biochars Containing Various Concentrations of Cadmium - Yuchao Fan; Xue Sheng; Ruizhi Xia; Tingting Dong; Shiwen Zhang; Xiujuan Feng; Jun Zhou; Guodong Fang; Hongbiao Cui (Bulletin of Environmental Contamination and Toxicology, 2025)

Equivalent mechanical parameters and representative elementary volume of rock masses material using a modified fabric tensor - Jinghan Yin; Zhen Cui; Qian Sheng; Xin Sun; Maochu Zhang (Computers and Geotechnics, 2025)

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)

Comprehensive assessment of carbon footprint and water footprint of ammonia synthetic process based on liquefied natural gas cold energy utilization - Qiming Wu; Yaru Zhou; Wenwu Xu; Yangyang Wang; Yangyang Liu; Yinglong Wang; Peizhe Cui; Sheng Yang; Bo Wang; Xiaolei Zhao (Fuel, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Biomass aerogel: An emerging eco-friendly material for adsorbing pollutants in water - Wei Liu; Chen Dai; Linheng He; Xingyu Liu; Zhiyang Zhao; Wenqian Yan; Man Yuan; Zihao Song; Sheng Cui (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

The Influence of Vickers Hardness and Brittleness on Particle Size Distribution During Ball Milling: A Multifractal Approach - Sheng Zhang; Yichao Rui; Zilong Zhou; Xin Cai; Hongzhi Cui (Rock Mechanics and Rock Engineering, 2025)

A Novel Rock Damping Ratio and Damping Coefficient Based on Linear Energy Damping Law - Haowei Yang; Bing Sun; Jie Cui; Sheng Zeng; Yi Shan (Rock Mechanics and Rock Engineering, 2025)

The potential impacts of climate change on the life history and habitat of jumbo flying squid in the southeast Pacific Ocean: overview and implications for fisheries management - Wei Yu; Xiaolin Feng; Jian Wen; Xiaoci Wu; Xingnan Fang; Jianan Cui; Zhiping Feng; Yilu Sheng; Zhengfang Zhao; Bilin Liu; Pengchao Jin; Guanyu Hu; et al. (Reviews in Fish Biology and Fisheries, 2025)

The pharmacokinetics, pharmacodynamics and tolerability of SHR6508 in chinese healthy subjects: a randomized, placebo-controlled, double-blind, single-dose and dose-escalation phase I trial - Sheng-ting Zhang; Hong-yi Tan; Shuang Yang; Xiao-yan Yang; Chang Cui; Jie Huang; Guo-ping Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Capabilities and Limitations of Air‐Dried Soils in Microbial Biogeography: A Regional‐Scale Comparative Analysis - Jianwei Zhang; Zhiying Guo; Jie Liu; Xianzhang Pan; Yanan Huang; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Jing Sheng (Environmental Microbiology, 2025)
Air‐dried soil archives offer valuable potential for studying long‐term microbial dynamics, yet systematic evaluations across large spatial scales with paired fresh‐soil comparisons remain limited. Here, we systematically evaluated the effects of 1‐month air‐drying on microbial biogeography across 244 paddy fields in eastern China. Results showed that air‐drying significantly altered communities by reducing diversity through the elimination of rare taxa while enriching desiccation‐resistant phyla like Firmicutes, Chloroflexi and Actinobacteria. These compositional shifts further triggered functional bias, enhancing fermentation/methanogenesis pathways while suppressing nitrogen cycling processes. Despite these alterations, air‐dried samples maintained remarkable fidelity to key ecological patterns observed in fresh soils. Multivariate analyses demonstrated strong structural concordance between paired samples, with soil pH consistently emerging as the primary environmental driver in both data sets. This preservation of biogeographical relationships occurred despite significant changes in underlying ecological mechanisms. Air‐dried soil communities exhibited increased stochastic assembly, reduced niche breadth and simplified co‐occurrence networks with altered keystone taxa, indicative of a two‐phase process: deterministic filtering of drought‐sensitive taxa followed by stochastic reorganisation among survivors. Overall, our findings provide a framework for utilising soil archives in microbial ecology, showing that while air‐drying introduces predictable distortions, samples retain essential ecological information for reconstructing historical microbial–environmental relationships at large scales.

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Synergistic interaction of BiOCl surface OVs and bulk OVs for photocatalytic mercury removal - Tianhui Cui; Chaofan Liu; Kai Huang; Jiang Wu; Sheng Wang; Yaji Huang; Shaohua Liang; Jingxin Xu; Xueli Sun; Xiuyong Zhao (Fuel, 2025)

RSTA: A reversible signal transmission architecture for breaking the limitation of unidirectional transmission - Xin Liu; Shuang Cui; Xun Zhang; Fuxing Zhou; Kaikai Sheng; Bin Wang; Qiang Zhang (Chemical Engineering Journal, 2025)

High near-infrared reflection characteristics and energy-saving applications of Bi-doped LaAlO3 perovskite yellow pigment - Cheng Cai; Yi Wu; Kangzhen Sun; Qiuli Fang; Pengzhai Li; Sheng Cui; Yin Zhang (Chemical Engineering Journal, 2025)

Construction of CA@MnO2 core-shell heterostructure for supercapacitor applications - Xiaochan Liu; Tingwei Wang; Xibin Yi; Jing Zhang; Xinfu Zhao; Sijia Liu; Sheng Cui (Chemical Engineering Journal, 2025)

Compressive stress induced by desiccation shrinkage in clayey soils - Hao Zeng; Chao-Sheng Tang; Yu-Jun Cui; Abdallah Najdi (Applied Clay Science, 2025)

Fruit Taste and Mineral Nutrition Characteristics of Different Pear Cultivars Grown in China - Li Junhao; Yang Sheng; Liu Shaohua; Cui Tingting; Li Liulin; Zhou Zhiqin (Applied Fruit Science, 2025)

Temperature-dependent soil storage: Changes in microbial viability and respiration in semiarid grasslands - Chen Tian; Dongqing Cui; Yue Cao; Sheng Luo; Huimin Song; Peizhi Yang; Yongfei Bai; Jianqing Tian (Soil Biology and Biochemistry, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

Evolution characteristics of microwave absorbing carbon material on surface of CoFe2O4@biochar during hydrogen production from methane decomposition process - Haipeng Cui; Song Hu; Tao Yang; Limo He; Kai Xu; Long Jiang; Sheng Su; Yi Wang; Jun Xu; Jun Xiang (Fuel, 2025)

Microbial diversity and antibacterial mechanism of slightly acidic electrolyzed water against Pseudomonas fluorescens in razor clam during storage - Xiaoting Xuan; Ziyi Zhang; Haitao Shang; Zheliang Sheng; Yan Cui; Xudong Lin; Shanqiao Chen; Lin Zhu (Food Research International, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Constructing robust multifunctional coating on wearable nylon/cotton blend fabrics for human thermal management, motion monitoring, fire safety, and water repellency - Jian Liu; Xiaowei Su; Qinyong Liu; Xinyu Cui; Hongfei Li; Xiaoyu Gu; Jun Sun; Sheng Zhang (Chemical Engineering Journal, 2025)

Hyperconnectivity and Connectome Gradient Dysfunction of Cerebello-Thalamo-Cortical Circuitry in Alzheimer’s Disease Spectrum Disorders - Chenyang Yao; Yi Shan; Bixiao Cui; Zhigeng Chen; Sheng Bi; Tao Wang; Shaozhen Yan; Jie Lu (The Cerebellum, 2025)

Genetic link between concealed granite and tin mineralization in the Yuling tin deposit, Nanling Range, South China: Constraints from zircon and cassiterite U-Pb dating, geochemistry, and Lu-Hf isotopes - Yong-Kang Chen; Pei Ni; Jun-Yi Pan; Yi-Ming Xu; Qi-Zhi Yang; Jian-Ming Cui; Wen-Sheng Li; Guan-Jian Fang (Journal of Geochemical Exploration, 2025)

Strengthened carbamazepine degradation via producing 1O2 with Ru-doped hollow tubular MoS2 under peroxymonosulfate activation - Yu Yin; Wenning Li; Bing Hu; Qinxin Wang; Abdul Hannan Asif; Lei Shi; Shu Zhang; Hongqi Sun; Sheng Cui (Journal of Environmental Chemical Engineering, 2025)

Bimetallic self-supported AuCu alloy aerogel with abundant diffusion channels for regulating oxygen reduction reaction by electronic structure modulation for zinc-air battery application - Ke Yuan; Yalei Zheng; Yihe Zhao; Liu Liu; Aleeza Altaf; Yanan Chen; Anquan Wang; Xiaodong Wu; Sheng Cui (Chemical Engineering Journal, 2025)

Advanced micro-textural engineering for the fabrication of high-performance superomniphobic surfaces - Chang Lv; Tao Wang; Yuanwei Ding; Haiyan Li; Yulong Ying; Lvlv Ji; Weihao Cui; Lei Liu; Sheng Wang (Chemical Engineering Journal, 2025)

Elaborate numerical analysis and new fibre Bragg grating monitoring methods for the ground pressure in shallow large-diameter shield tunnels: a case study of the yellow crane tower tunnel project - Leyang Fan; Lan Cui; Zeqi Zhu; Qian Sheng; Junjie Zheng; Youkou Dong (Bulletin of Engineering Geology and the Environment, 2025)

Erosion–Seepage System (ESS) for Flow-Induced Soil Erosion Rate with Seepage - Yuhuan Zhang; Lin Cui; Dong-Sheng Jeng; Zheng Wang; Hualing Zhai (Journal of Marine Science and Engineering, 2025)
Critical shear stress and erosion rate are two key factors for the prediction of the incipient motion of sediment and the transport of sediment. Seabed seepage can significantly alter the pore pressure gradient within the soil and the hydrodynamics around the surface of the seabed, further affecting erosion processes. Previous studies attempted to theoretically clarify the effect of the seepage force on sediment incipient motion. In this study, a newly designed erosion–seepage system (ESS) that considers the effect of seepage under steady or oscillatory flow is used to simulate the erosion process. Through the designed ESS, the erosion height per unit time was measured directly on the Yellow River sand, and the upward seepage force was applied at the bottom of the soil sample in the process. Then, the relationship between the erosion rate and seepage was established.The experimental results show that upward seepage reduces the critical shear stress of the sand bed and increases the erosion rate of the soils under both steady flow and oscillatory flow conditions. The erosion coefficients in the erosion models decrease with increasing seepage gradient. The effect of seepage on erosion is more obvious when the flow velocity of the steady stream is large, while the effect of seepage on erosion is relatively small under the oscillatory state with a shorter period. However, when violent erosion of soil samples occurs, seepage under both flow conditions greatly increases the erosion rate.

Wastewater treatment performance and greenhouse gas emissions in constructed wetlands with different plant species across varying influent concentrations - Hu Cui; Si-Le Hu; Sheng-Nan Hou; Xin-Yi Wang; Jun-Feng Wang; Hui Zhu (Journal of Water Process Engineering, 2025)

Microbial fuel cell-assisted composting yields higher performance on metals passivation, antibiotics degradation, and resistance genes removal - Hu Cui; Sheng-Nan Hou; Xin-Yi Wang; Lei Li; Xiao-Hu Dai; Hui Zhu (Environmental Research, 2025)

Integrated STL-DBSCAN algorithm for online hydrological and water quality monitoring data cleaning - Chenyu Song; Jingyuan Cui; Yafei Cui; Sheng Zhang; Chang Wu; Xiaoyan Qin; Qiaofeng Wu; Shanqing Chi; Mingqing Yang; Jia Liu; Ruihong Chen; Haiping Zhang (Environmental Modelling & Software, 2025)

A logistic-Lasso-regression-based seismic fragility analysis method for electrical equipment considering structural and seismic parameter uncertainty - Jiawei Cui; Ailan Che; Sheng Li; Yongfeng Cheng (Earthquake Engineering and Engineering Vibration, 2025)

Experimental Study of Submarine Pipeline with Geotextile and Stone Cover Protection Under the Superposition of Waves and Currents - Wenqi Si; Mingqing Wang; Yaru Gao; Ke Sun; Bing Chen; Risheng Wang; Lin Cui; Dong-Sheng Jeng; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
Submarine pipelines are the main transport carriers of marine resources. In order to protect these pipelines, geotextile and stone covering measures are adopted in this paper and the protective effect is studied. A sequence of physical model tests was conducted to carry out the research. The hydrodynamic characteristics and seabed oscillation response of the seabed surrounding the pipeline were analyzed with or without geotextile and stone cover protection, and it was found that they were affected by waves (and currents). The experimental results show the following: (1) comparing the regular wave and current with the regular wave alone, it is found that forward current promotes wave propagation and reverse current inhibits wave propagation; (2) the protective effect of geotextile and stone covering measures on different positions of the pipeline (the front, the bottom, and the back of the pipe) is basically same; (3) in the case of waves with large wave heights and long wave periods superimposed with ocean currents, the protective effect of geotextile and stone coverings on the hydrodynamic and seabed pore pressure around the pipeline is more significant.

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Nitrogen uptake by Scenedesmus quadricauda and its responses over environmental factors - Pengbo Zhao; Xiaofei Lou; Yafei Cui; Chang Wu; Chenyu Song; Jingyuan Cui; Sheng Zhang; Yao Qu; Tao Peng; Ruihong Chen; Haiping Zhang (Marine Pollution Bulletin, 2024)

Inhibition of ATP1V6G3 prompts hepatic stellate cell senescence with reducing ECM by activating Notch1 pathway to alleviate hepatic fibrosis - Xiao-Pei Xue; Yu Sheng; Qi-Qi Ren; Shi-Meng Xu; Min Li; Zhao-Xiu Liu; Cui-Hua Lu (Tissue and Cell, 2024)

Advancements and future perspectives of human tandem repeats - Wenbin Ye; Jason Sheng Li; Wei Li; Ya Cui (Science Bulletin, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Synergistic effects of microplastics and sulfonamide on greenhouse gas emissions in agricultural ditch sediments: Insights into microbial interactions - Yu-Ting Shen; Sheng-Nan Hou; Ya-Qin Miao; Xing-Yi Wang; Hu Cui; Hui Zhu (Journal of Hazardous Materials, 2024)

A free radical interlocking co-deposition strategy based on the oxidative pyrolysis mechanism of polyethylene terephthalate to achieve green energy recovery - Weiwen Gu; Tianyi Ma; Xinyu Cui; Xiaoyu Gu; Jun Sun; Jinping Xiong; Rui Wang; Sheng Zhang (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Trade-offs between Cd bioconcentration and translocation and underlying physiological and rhizobacterial mechanisms in Phragmites australis - Meiqi Yin; Xiya Zhang; Hong Zhu; Wenyi Sheng; Yiming Wu; Dongzi Jiang; Qishen Wen; Hongjin Shao; Yaolin Guo; Cui Wang; Luyao Ma; Xiaona Yu; et al. (Journal of Environmental Management, 2024)

Niche-specific evolution and gene exchange of Salmonella in retail pork and chicken - Huanjing Sheng; Linna Zhao; Jia Suo; Qiuping Yang; Chenyang Cao; Jia Chen; Guangqing Cui; Yiling Fan; Yi Ma; Shengnan Huo; Xin Wu; Tao Yang; et al. (Food Research International, 2024)

Circular RNA and its potential diagnostic and therapeutic values in breast cancer - Di Gao; Can Cui; Yaoxuan Jiao; Han Zhang; Min Li; Junjie Wang; Xiumei Sheng (Molecular Biology Reports, 2024)

Bleomycin induces endothelial cell pyroptosis and regulates fibrosis by activating the NLRP3/caspase-1/GSDMD pathway: a possible mechanism contributing to the sclerotherapy of venous malformations - Sheng Chen; Yuan Wang; Qingwen Gao; Jie Cui; Weimin Shen (Journal of Molecular Histology, 2024)

Research on the Separation Technology of Kelp and Shellfish Box Based on Shellfish–Kelp Mixed Culture Mode - Yanan Wang; Zehao Zha; Xian Wang; Yipeng Cui; Xinxin Wang; Duanyang Geng; Hua Zhou; Tongfei Sheng (Fishes, 2024)
Aiming at the problem of floating shellfish boxes interfering with kelp harvesting when mechanized kelp harvesting is based on shellfish–kelp mixed culture mode, this paper combines the structural characteristics of the shellfish box itself, designs the kelp harvesting unit test bench and develops a shellfish box separator device. The key factors affecting the box separator’s separation effect were derived through the theoretical analysis. The process of separation of a shellfish box by the box separator is simulated and optimized under the derived boundary conditions. The single-factor test for the separating effect of the box separator was conducted with ADAMS kinematics simulation software. The test showed the optimal utility intervals for the key factors under consideration. Further orthogonal tests were conducted for the three key factors, which were ranked in descending order of importance as box separator separation angle θ, box separator taper angle β and box separator placement depth h. The optimal parameter combination is the box separator separation angle of 31.9°, the box separator taper angle of 30° and the box separator placement depth of 550 mm. Verification experiments have shown that both indicators, the farthest horizontal distance of the shellfish box and the angle of the shellfish box deviating from the box separator, meet the actual production requirements. In summary, the separator can effectively separate the shellfish box from the kelp, and the device is simple in design, quick in operation, and accomplished separation without disturbing shellfish. This study can provide a theoretical basis for the separation technology of kelp and shellfish box under shellfish–kelp mixed culture mode.

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Microplastics in the atmospheric of the eastern coast of China: different function areas reflecting various sources and transport - Sheng Xu; Bowen Cui; Weixin Zhang; Ruijing Liu; Hao Liu; Xiaowei Zhu; Xuqing Huang; Minyi Liu (Environmental Geochemistry and Health, 2024)

Long-term organic fertilization increases phosphorus content but reduces its release in soil aggregates - Hu Cui; Brian Shutes; Sheng-Nan Hou; Xin-Yi Wang; Hui Zhu (Applied Soil Ecology, 2024)

Influence of sea ice on ship routes and speed along the Arctic Northeast Passage - Yaqing Shu; Hailong Cui; Lan Song; Langxiong Gan; Sheng Xu; Jie Wu; Chunmiao Zheng (Ocean & Coastal Management, 2024)

Influence of γ-PGA on greenhouse gas emissions and grain yield from paddy rice under different rice varieties - Shi-hao Li; Cui-hua Yang; Xu-xu Yi; Fei-xiong Zheng; Xue-zhu Du; Feng Sheng (Science of The Total Environment, 2024)

Partial dynamic ( u − p ) integrated model for both oscillatory and residual soil response in a poro-elastic seabed - Zhipeng Wan; Lin Cui; Dong-Sheng Jeng (Ocean Engineering, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Decoding the fish genome opens a new era in important trait research and molecular breeding in China - Qian Zhou; Jialin Wang; Jiongtang Li; Zhangfan Chen; Na Wang; Ming Li; Lei Wang; Yufeng Si; Sheng Lu; Zhongkai Cui; Xuhui Liu; Songlin Chen (Science China Life Sciences, 2024)

Experimental Study of the Random Wave-Induced Hydrodynamics and Soil Response in a Porous Seabed Around Double Piles - Mingqing Wang; Wenqi Si; Yaru Gao; Lin Cui; Dong-Sheng Jeng; Ke Sun; Bing Chen; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
The evaluation of the wave-induced pore pressures around the offshore piles has attracted great attentions among coastal engineers, because they have been commonly used as foundations of numerous marine infrastructures. This paper presents comparative studies of the random wave-induced transient seabed response around single and double piles in a sandy seabed through a series of wave flume experiments. The influences of relative spacing ratios, wave incidence angles, and front pile diameters under different random wave parameters on oscillatory pore pressures in the vicinity of double piles are examined. In addition, variations in wave profiles and dynamic wave pressures surrounding single and double piles are quantitatively analyzed. Based on the experimental results, the following conclusions can be drawn: (1) under the influence of random waves, the wave profiles around the double piles exhibit obvious irregularity and nonlinearity; (2) the shielding effect existing in the tandem piles results in lower dynamic wave pressures around the rear pile compared to the front pile; (3) the pore pressures on the front surface of the double piles decrease with increasing soil depth, with a decreasing attenuation rate at each layer; (4) when the relative spacing ratio G/D2=3, the group-pile effect weakens, leading to an increase in the pore pressures around the rear pile, approaching the results of a single pile under conditions of lower significant wave heights or periods; (5) the intense disturbance effect caused by large wave incidence angles exacerbates the pore pressure response around the double piles; (6) when the diameter of the front pile in the tandem piles increases, it enhances the shielding effect, thus suppressing the seabed response around the rear pile. In contrast, it causes an increase in the wave surface around the double piles, exacerbating the pore pressure response in the seabed. The latter effect becomes more pronounced when the significant wave height is larger.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Numerical and physical implementation of controlled stress wave excitation and waveform effect in SHPB system - Chun-yang Cui; Xiang-shang Li; Jia-min Wang; Mei-mei Wang; Wei-yu Zheng; Wei-sheng Du (International Journal of Rock Mechanics and Mining Sciences, 2024)

Characterization, hazard identification, and risk assessment of volatile organic compounds in Poly(butylene adipate-co-terephthalate)-based food contact articles - Hanke Li; Hongjian Miao; Lichang Chen; Qi-Zhi Su; Zhenwei Liu; Canghao Xie; Jinxin Liang; Siliang Wu; An-Qi Cui; Can Xu; Ben Dong; Dan Li; et al. (Food and Chemical Toxicology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Dynamic damage and fracture mechanism of curved ripper cutting reinforced concrete composites: Numerical simulation combined with engineering practice - Yingran Fang; Xinggao Li; Lunmeng Cui; Yidong Guo; Jun Mei; Changshun Zhang; Sheng Zhang (Tunnelling and Underground Space Technology, 2024)

Flexible nanoimprint lithography enables high-throughput manufacturing of bioinspired microstructures on warped substrates for efficient III-nitride optoelectronic devices - Siyuan Cui; Ke Sun; Zhefu Liao; Qianxi Zhou; Leonard Jin; Conglong Jin; Jiahui Hu; Kuo-Sheng Wen; Sheng Liu; Shengjun Zhou (Science Bulletin, 2024)

Specific roles of lattice oxygen and asymmetric interface Cu-[Ox]-Ce structure-relating chemisorbed oxygen over CuO/CeO2 on the catalysis of benzene combustion - Jiancai Hou; Jiangliang Hu; Xinmin Cui; Shasha Du; Dongxia Wu; Liping Chang; Sheng Wang; Weiren Bao; Jiancheng Wang (Fuel, 2024)

In vitro fermentation characteristics and interaction of neutral and acidic polysaccharides from Lycii fructus on human gut microbiota - Xiaofei Liang; Mengqiu Liu; Anni Yao; Wanchen Cui; Yan Wei; Sheng Guo; Jialun Duan; Hongjie Kang; Xueyi Zhou; Shulan Su; Heiying Jin; Fang Zhang; et al. (Food Hydrocolloids, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Water purification capacity of ecological ditch: A systematic review and meta-analysis of influencing factors - Yu-Ting Shen; Sheng-Nan Hou; Si-Le Hu; Ya-Qin Miao; Hu Cui; Hui Zhu (Ecological Engineering, 2024)

Eco-friendly wearable textiles: Asymmetric structures for EMI shielding, thermal management, and fire safety - Jian Liu; Jingfan Zhang; Xinyu Cui; Weiwen Gu; Qinyong Liu; Hongfei Li; Xiaoyu Gu; Jun Sun; Sheng Zhang (Chemical Engineering Journal, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Ruthenium decorated nickel-iron layered double hydroxides (NiFe-LDH) for promoting peroxymonosulfate activation and atrazine degradation - Yu Yin; Shuting Pan; Jiajie Lu; Abdul Hannan Asif; Sheng Cui; Shaobin Wang; Hongqi Sun (Journal of Environmental Chemical Engineering, 2024)

Ionic liquid-based advanced porous organic hyper-crosslinked polymers (ILHCPs) for CO2 capture and conversion - Ruina Zhang; Guokai Cui; Xiuqin Wang; Yinfeng Chen; Xinjie Qiu; Quanli Ke; Dongshun Deng; Chunliang Ge; Hanfeng Lu; Sheng Dai (Chemical Engineering Journal, 2024)

Total coliforms, microbial diversity and multiple characteristics of Salmonella in soil-irrigation water-fresh vegetable system in Shaanxi, China - Qiuping Yang; Jin Chen; Jinghan Dai; Yuanjie He; Kexin Wei; Mengqing Gong; Qinquan Chen; Huanjing Sheng; Li Su; Lisha Liu; Jia Chen; Li Bai; et al. (Science of The Total Environment, 2024)

Soil amendments reduce CH4 and CO2 but increase N2O and NH3 emissions in saline-alkali paddy fields - Hu Cui; Hui Zhu; Fu-Man Zhang; Xin-Yi Wang; Sheng-Nan Hou; Wei-Dong Feng (Science of The Total Environment, 2024)

Photochemical processes transform dissolved organic matter differently depending on its initial composition - Sheng-Ao Li; Qianru Wang; Hua Ma; Xinghong Cao; Yingyue Song; Fuyi Cui; Andrew J. Tanentzap (Science of The Total Environment, 2024)

Increased CO2 capture capacity via amino-bifunctionalized halloysite nanotubes adsorbents - Zengli Wang; Yaheng Pang; Hongxia Guo; Huan Wang; Li Liu; Xiao Wang; Sheng Zhang; Wenquan Cui (Fuel, 2024)

Self-cleaning, energy-saving aerogel composites possessed sandwich structure: Improving indoor comfort with excellent thermal insulation and acoustic performance - Zihao Song; Lei Su; Man Yuan; Sisi Shang; Sheng Cui (Energy and Buildings, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Electroacupuncture Exerts Analgesic Effects by Restoring Hyperactivity via Cannabinoid Type 1 Receptors in the Anterior Cingulate Cortex in Chronic Inflammatory Pain - Junshang Wu; Libo Hua; Wenhao Liu; Xiaoyun Yang; Xiaorong Tang; Si Yuan; Sheng Zhou; Qiuping Ye; Shuai Cui; Zhennan Wu; Lanfeng Lai; Chunzhi Tang; et al. (Molecular Neurobiology, 2024)
As one of the commonly used therapies for pain-related diseases in clinical practice, electroacupuncture (EA) has been proven to be effective. In chronic pain, neurons in the anterior cingulate cortex (ACC) have been reported to be hyperactive, while the mechanism by which cannabinoid type 1 receptors (CB1Rs) in the ACC are involved in EA-mediated analgesic mechanisms remains to be elucidated. In this study, we investigated the potential central mechanism of EA analgesia. A combination of techniques was used to detect the expression and function of CB1R, including quantitative real-time PCR (q-PCR), western blot (WB), immunofluorescence (IF), enzyme-linked immunosorbent assay (ELISA), and in vivo multichannel optical fibre recording, and neuronal activity was examined by in vivo two-photon imaging and in vivo electrophysiological recording. We found that the hyperactivity of pyramidal neurons in the ACC during chronic inflammatory pain is associated with impairment of the endocannabinoid system. EA at the Zusanli acupoint (ST36) can reduce the hyperactivity of pyramidal neurons and exert analgesic effects by increasing the endocannabinoid ligands anandamide (AEA), 2-arachidonoylglycerol (2-AG) and CB1R. More importantly, CB1R in the ACC is one of the necessary conditions for the EA-mediated analgesia effect, which may be related to the negative regulation of the N-methyl-D-aspartate receptor (NMDAR) by the activation of CB1R downregulating NR1 subunits of NMDAR (NR1) via histidine triad nucleotide-binding protein 1 (HINT1). Our study suggested that the endocannabinoid system in the ACC plays an important role in acupuncture analgesia and provides evidence for a central mechanism of EA-mediated analgesia.

Fluid inclusion constraint on sulfide precipitation in wolframite-quartz veins: A case study of the giant Dajishan W polymetallic deposit, South China - Jian-Ming Cui; Pei Ni; Jun-Yi Pan; Wen-Sheng Li (Journal of Geochemical Exploration, 2024)

Quantifying denudation rates and sediment recycling of low-relief, high-elevation landscapes using in-situ and meteoric cosmogenic nuclides - Ye Yang; Shun-Cheng Zhang; Jia-Xin Zhang; Li-Feng Cui; Cong-Qiang Liu; Sheng Xu (Geochimica et Cosmochimica Acta, 2024)

Prediction of transformation in the histopathological growth pattern of colorectal liver metastases after chemotherapy using CT-based radiomics - Shengcai Wei; Xinyi Gou; Yinli Zhang; Jingjing Cui; Xiaoming Liu; Nan Hong; Weiqi Sheng; Jin Cheng; Yi Wang (Clinical & Experimental Metastasis, 2024)

Exogenous melatonin enhanced cadmium stress tolerance of cucumber seedlings (Cucumis sativus L.) - Xin Kang; Zi-Qi Pei; Ting-Ting Xu; Cui-Yun Dong; Xue Bai; Cheng Ma; Qiao Zhu; Cai-Hong Chai; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Biologia, 2024)

Metal element-based adsorbents for phosphorus capture: Chaperone effect, performance and mechanism - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Chemosphere, 2024)

Bamboo classification based on GEDI, time-series Sentinel-2 images and whale-optimized, dual-channel DenseNet: A case study in Zhejiang province, China - Bo Wang; Hong Zhao; Xiaoyi Wang; Guanting Lyu; Kuangmin Chen; Jinfeng Xu; Guishan Cui; Liheng Zhong; Le Yu; Huabing Huang; Qinghong Sheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

pH-responsive multi-network composite cellulose-based hydrogels for stable delivery of oral IgY-Fab fragments - Minquan Xia; Zhaoyu Cui; Tao Zeng; LiZhi Lu; Long Sheng; Zhaoxia Cai (Food Chemistry, 2024)

Chemical-free vacuum ultraviolet irradiation as ultrafiltration membrane pretreatment technique: Performance, mechanisms and DBPs formation - Shengnan Chen; Xin Sheng; Zhiwei Zhao; Fuyi Cui (Journal of Environmental Management, 2024)

Influence of inertinite on coal physicochemical thermal transformation properties and liquefaction behaviors - Wenchao Qian; Chunyang Yan; Xiaoyin Mu; Jiahao Chen; Lulu Cui; Hualin Lin; Sheng Han; Zongqing Bai (Fuel, 2024)

Insight into hydrogen production through halotolerant and cellulose-degrading Clostridium thermopalmium - Sheng-Jie Chen; Ming-Jun Zhu; Si-Ying Cui (Chemical Engineering Journal, 2024)

Regulation of Hepatocellular Cholesterol Metabolism By Lactobacillus Paracasei BY2 and Its Embedding Delivery - Hua-Ling Cui; Meng-Fan Li; Sheng-Ya Liu; Ming Yu; Wen-Yong Lou (Probiotics and Antimicrobial Proteins, 2024)

Utilization of 3D printing technology in hepatopancreatobiliary surgery - Wujiang Shi; Jiangang Wang; Jianjun Gao; Xinlei Zou; Qingfu Dong; Ziyue Huang; Jialin Sheng; Canghai Guan; Yi Xu; Yunfu Cui; Xiangyu Zhong (Journal of Zhejiang University-SCIENCE B, 2024)

Leveraging CRISPR/Cas12 signal amplifier to sensitive detection of apurinic/apyrimidinic endonuclease 1 and high-throughput inhibitor screening - Sheng Ding; Yi Yuan; Juan Dong; Feng Du; Xin Cui; Zheng Shi; Zhuo Tang (Analytica Chimica Acta, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

3D Printing windows and rheological properties for normal maize starch/sodium alginate composite gels - Ying Cui; Fan Yang; Chang-sheng Wang; Andreas Blennow; Changyong Li; Xingxun Liu (Food Hydrocolloids, 2024)

Baicalin exerts neuroprotective actions by regulating the Nrf2-NLRP3 axis in toxin-induced models of Parkinson's disease - Jiahua Huang; Xinyue Zhang; Xueping Yang; Qingyun Yv; Fanlong Ye; Sheng Chen; Ying Cui; Linting Gu; Min Zhu; Wenwei Li (Chemico-Biological Interactions, 2024)

Ecological risk, dynamics in fingerprinting, and source apportionment of heavy metals in soils from plateau in Upper Yellow River, Qinghai Province, China - Chunyu Hua; Haiyan Sheng; Jingyu He; Zhaotong Fang; Mengyuan Zhu; Zhaojie Cui; Lijun Ren (Journal of Soils and Sediments, 2024)

Taurine promotes insulin synthesis by enhancing Isl-1 expression through miR-7a/RAF1/ERK1/2 pathway - Hui Liu; Tongjuan Niu; Guobin Qiu; Sheng Cui; Di Zhang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Study on shear mechanical characteristic evolution and influencing factors of rock joint surfaces under cyclic loading conditions - Jinghan Yin; Zhen Cui; Qian Sheng; Jian Chen; Maochu Zhang (Bulletin of Engineering Geology and the Environment, 2024)

A Novel Deformation Analytical Solution and Constitutive Model for Fractured Rock Masses - Zeqi Zhu; Lan Cui; Youkou Dong; Qian Sheng; Kaiwei Tian; Zhenshan Guo (Journal of Marine Science and Engineering, 2023)
In order to study the deformation and stability of a fractured rock mass, existing research suggests that fracture deformation, which is usually obtained by evaluating the equivalent deformation modulus, dominates the deformation of a fractured rock mass. However, this parameter is difficult to obtain in theory and practice, which limits the application of rock mass deformation analysis methods. In order to calculate the deformation of fractured rock masses, the mass of the rock is regarded as a sponge-like material, and it is assumed that the deformation of a water-saturated fractured rock mass under external force load is approximately equal to the net flow of fracture water. Based on this assumption, firstly, the relationship between rock mass deformation and fracture flow is studied through a single-fracture rock mass model. The hydraulic properties of the fracture are characterized by the permeability coefficient, and the fracture deformation in the rock mass is equivalent to the fracture flow. The fracture deformation calculation formula is derived from the fracture hydraulics calculation formula, and this is compared with the measured data. The rationality of the calculation formula was verified. On this basis, the calculation formula for rock mass deformation, including multiple groups of fracture surfaces, is proposed, and the stress-strain constitutive relationship of a complex rock mass is established. The correctness of the calculation method was verified by comparing it with other theoretical calculation results.

Rationally designed calcium carbonate multifunctional trap for contaminants adsorption - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Science of The Total Environment, 2023)

Soil aggregate-driven changes in nutrient redistribution and microbial communities after 10-year organic fertilization - Hu Cui; Hui Zhu; Brian Shutes; Alain N. Rousseau; Wei-Dong Feng; Sheng-Nan Hou; Yang Ou; Bai-Xing Yan (Journal of Environmental Management, 2023)

Improved eutrophication model with flow velocity-influence function and application for algal bloom control in a reservoir in East China - Jingyuan Cui; Hanling Xu; Yafei Cui; Chenyu Song; Yao Qu; Sheng Zhang; Haiping Zhang (Journal of Environmental Management, 2023)

Calibration of the carbonate clumped isotope thermometer of land snail shells - Rui Bao; Xuefen Sheng; Chenglong Li; Can Cui; Hao Yan; Junfeng Ji; Jun Chen (Chemical Geology, 2023)

Deep utilization of salinity gradient energy between concentrated seawater and river water by multi-stage reverse electrodialysis - Zhi-Yuan Guo; Wei-Zhe Cui; Zhi-Yong Ji; Kaniki Tumba; Jing Wang; Liu-Jia Fu; Zhao-Xiang Zhang; Jie Liu; Ying-Ying Zhao; Zhong-De Zhang; Jun-Sheng Yuan (Desalination, 2023)

Functional separator with 1 T/2H-MoSe2 nanosheets decorated nitrogen and sulfur co-doped mesoporous hollow carbon spheres for high-performance Li-S batteries - Qidong Sheng; Hui Liu; Yaning Liu; Bo Jin; Mengyang Cui; Yiyang Li; Nan Gao; Xingyou Lang; Qing Jiang (Chemical Engineering Journal, 2023)

FeCa-based layered double hydroxide, a high-performance phosphorus adsorbent in constructed wetlands and ecological dams - A pilot scale study - Wei-Dong Feng; Hu Cui; Hui Zhu; Brian Shutes; Bai-Xing Yan; Sheng-Nan Hou (Chemosphere, 2023)

Application of metaheuristic optimization algorithms-based three strategies in predicting the energy absorption property of a novel aseismic concrete material - Xiancheng Mei; Chuanqi Li; Zhen Cui; Qian Sheng; Jian Chen; Shaojun Li (Soil Dynamics and Earthquake Engineering, 2023)

Multi-objective optimization study of wave elimination and electricity generation performance of Savonius hydrokinetic turbine based on metamodel - Ruiyin Song; Boyu Liu; Zhuangzhuang Yang; Congjie Ren; Xi Cui; Yong Sheng (Ocean Engineering, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Prevalence, antibiotic susceptibility and genomic analysis of Salmonella from retail meats in Shaanxi, China - Huanjing Sheng; Jia Suo; Jinghan Dai; Siyue Wang; Mei Li; Li Su; Mengyuan Cao; Yanwei Cao; Jia Chen; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2023)

Viability of Lactobacillus acidophilus in Thin-Film Freeze-Dried Powders Filled in Delayed-Release Vegetarian Capsules in a Simulated Gastric Fluid - Jie-Liang Wang; Benjamin Southard; Miguel O. Jara; Yu-Sheng Yu; Haiyue Xu; Justin Kalafat; Robert O. Williams; Zhengrong Cui (AAPS PharmSciTech, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Dual-modal artificial synapse based on a lead-free halide Cu2AgBiI6 for image processing and information encryption - Shuaifei Mao; Mingqing Cui; Sheng Jiang; Pengfei Zhao; Jie Lao; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Jadranka Travas-sejdic; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2023)

Numerical simulation on the impact characteristics between rockfalls of different shapes and gravel cushions - Chun Zhu; Jia-jun Xu; Ya-jun Wang; Man-chao He; Sheng-hua Cui; Xiao-hu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2023)

Improved equations of ground pressure for shallow large-diameter shield tunnel considering multiple impact factors - Lan Cui; Wenyu Yang; Junjie Zheng; Qian Sheng (Tunnelling and Underground Space Technology, 2023)

A novel mussel-inspired layered montmorillonite-based composite aerogel for high-efficiency removal of heavy metal ions - Man Yuan; Xin Ye; Zihao Song; Limin Che; Sisi Shang; Meiyu Yuan; Shucai Wu; Dongsheng Liu; Sheng Cui (Journal of Water Process Engineering, 2023)

Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology - Xin-Ru Cui; Yu-Sheng Wang; Yan Chen; Hong-Yan Mu; Hai-Hua Chen (Food Hydrocolloids, 2023)

Assessment of Wave–Current-Induced Liquefaction under Twin Pipelines Using the Coupling Model - Jiayi Zhang; Lin Cui; Hualing Zhai; Dong-Sheng Jeng (Journal of Marine Science and Engineering, 2023)
Although twin pipelines in series have been used to transport hydrocarbons in engineering practice, most previous studies focused on the dynamic response of the seabed around a single pipeline. A two-way coupling model of fluid–structure–seabed interaction (FSSI) is proposed for the study of the soil response and liquefaction caused by waves and currents around twin pipelines. The present model integrates the flow model and the seabed model by introducing a boundary condition of velocity continuity in addition to the continuity of pressures at the seabed surface. Then, the inconsistency between the physical process and numerical simulation can be overcome in the one-way coupling model. Through a series of numerical simulations, the influence of different flow characteristics, soil properties, and pipeline configurations on the seabed response under the two-way coupling process were explored, and compared with the results of the single pipeline. The numerical results indicate that the twin pipeline configuration significantly alters the relevant responses compared to the single pipeline configuration, including the after-consolidation state, amplitude of velocity at the seabed surface, and distribution of pore pressure in the seabed. The parametric studies show that the amplitudes of the wave and current have significant impacts on the distribution of pore pressure in the seabed. The pore pressure in the seabed increases with the increase of forward wave current, while the results of reverse wave current are the opposite. In addition, the liquefaction range around the pipeline increases with the increase of Hw and Tw, and increases with the decrease of Sr and ks. At the same time, the gaps (G) and the ratio of pipe radius (R1/R2) between the twin pipelines also significantly affect the seabed response and liquefaction distribution around the pipeline.

Consumer preferences for oyster trait attributes in China: A choice experiment - Bin Yuan; Yuhu Cui; Wei Liu; Wenqian Sheng; Hanxiao Xu; Lin Yang (Aquaculture, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Global plastic upcycling during and after the COVID-19 pandemic: The status and perspective - Anni Li; Haiyang Cui; Yijie Sheng; Jie Qiao; Xiujuan Li; He Huang (Journal of Environmental Chemical Engineering, 2023)

Degradation bensulfuron-methyl by magnetic CoFe alloy@N-doped graphitized carbon derived from CoFe2O4 activated by peroxymonosulfate - Jialing Sheng; Shuke Guo; Chao Yuan; Xinrong Nie; Peilei Cui; Hongmei Jiang (Chemical Engineering Journal, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Late Carboniferous extension-related magmatism in the southwestern Alxa block of NW China: geochronology, geochemistry, and tectonic implications - Zeng-Zhen Wang; Xuan-Hua Chen; Wei-Cui Ding; Bing Li; Yi-Ping Zhang; Zhao-Gang Shao; Sheng-Lin Xu (International Geology Review, 2023)

Toxicity mechanism of peri-implantation pesticide beta-cypermethrin exposure on endometrial remodeling in early pregnant mice - Yong-Jiang Zhou; Qian-Feng Qiao; Li-Qing Wang; Tao-Yu Sheng; Man-Xue Cui; Qi-Duo Chen; Can-Yang Wang; Yun-Xiao Zhang (Toxicology, 2023)

Distribution and interaction characteristics of water quality at the stratified confluence reservoirs - Xia Shen; Sheng Li; Huanjie Cai; Zhi Li; Ningbo Cui (Journal of Hydrology, 2023)

Insight into mechanochemical destruction of PFOA by BaTiO3: An electron-dominated reduction process - Li Li; Ruoning Guo; Jie Gao; Jie Liu; Zhiwei Zhao; Xin Sheng; JunYu Fan; Fuyi Cui (Journal of Hazardous Materials, 2023)

Determination of dry soil layer and its soil heat flux distribution using actively heated distributed temperature sensing - Meng-Ya Sun; Bin Shi; Yu-Jun Cui; Chao-Sheng Tang; Xing Zheng; Jin Liu; Zi Ying; Yi-Jie Sun; Yun-Qiang Wang; Jing-Xiong Zhou (Engineering Geology, 2023)

Integrated Model for Wave-Induced Oscillatory and Residual Soil Response in a Poro-Elastic Seabed: Partially Dynamic Model - Zhipeng Wan; Lin Cui; Dong-Sheng Jeng (Journal of Marine Science and Engineering, 2023)
The evaluation of wave-induced residual pore pressure in a porous seabed and associated seabed liquefaction is essential for designing marine infrastructure foundations. The strength and stiffness of the seabed could be weakened due to the build-up of pore pressures under cyclic wave action, further leading to residual liquefaction. Existing models for residual liquefaction are limited to the quasi-static uncoupled approaches, which do not account for the effect of oscillatory pore pressure on the accumulative pore pressure acceleration of solid particles, despite the mutual influence of these two mechanisms. To overcome these limitations, this paper proposes a new model for residual soil response with u−p approximation (partial dynamic model) that couples oscillatory and residual mechanisms. The proposed model is validated through wave flume tests and centrifuge tests. Based on the coupling model, a new criterion of liquefaction integrating both oscillatory and residual mechanisms is also proposed. Numerical examples demonstrate that the coupling effect significantly affects the wave-induced seabed liquefaction potential. Furthermore, a new parameter (Ω) representing the ratio of oscillatory and residual pore pressure is introduced to clarify which mechanism dominates the pore pressure development.

Building of soft-hard compound brush in porous PVA/NH2@TAtZnO plural gel and the high-efficiency anti-interference removal on Pb(II) - Lingli Liu; Sheng Xu; Zhenxi Wang; Xiaoguang Chen; Meng Cao; Shangxi Zhang; Yang Liu; Jinlong Cui (Chemosphere, 2023)

Structural characterization on a β-agarase Aga86A_Wa from Wenyingzhuangia aestuarii reveals the prevalent methyl-galactose accommodation capacity of GH86 enzymes at subsite −1 - Yuying Zhang; Sheng Dong; Guangning Chen; Siqi Cao; Jingjing Shen; Xuanwei Mei; Qiu Cui; Yingang Feng; Yaoguang Chang; Yanchao Wang; Changhu Xue (Carbohydrate Polymers, 2023)

Microvibration transfer and suppression of satellite under multi-source coupling disturbances based on energy flow analysis - Yan Shen; Yang Xu; Xiaowei Sheng; Peibo Li; Zheng Cui (Advances in Space Research, 2023)

Insights into the characteristics of primary radioresistant cervical cancer using single-cell transcriptomics - Biyuan Xing; Congli Pu; Yunshang Chen; Yuhan Sheng; Baofang Zhang; Jie Cui; Gang Wu; Yingchao Zhao (Human Cell, 2023)
Radioresistance is a major cause of radiotherapy failure among patients with cervical cancer (CC), the fourth most common cause of cancer mortality in women worldwide. Traditional CC cell lines lose intra-tumoral heterogeneity, posing a challenge for radioresistance research. Meanwhile, conditional reprogramming (CR) maintains intra-tumoral heterogeneity and complexity, as well as the genomic and clinical characteristics of original cells and tissues. Three radioresistant and two radiosensitive primary CC cell lines were developed under CR conditions from patient specimens, and their characteristics were verified via immunofluorescence, growth kinetics, clone forming assay, xenografting, and immunohistochemistry. The CR cell lines had homogenous characteristics with original tumor tissues and maintained radiosensitivity in vitro and in vivo, while also maintaining intra-tumoral heterogeneity according to single-cell RNA sequencing analysis. Upon further investigation, 20.83% of cells in radioresistant CR cell lines aggregated in the G2/M cell cycle phase, which is sensitive to radiation, compared to 38.1% of cells in radiosensitive CR cell lines. This study established three radioresistant and two radiosensitive CC cell lines through CR, which will benefit further research investigating radiosensitivity in CC. Our present study may provide an ideal model for research on development of radioresistance and potential therapeutic targets in CC.

Characteristics of dynamic shear modulus and damping ratio and the structural formula of EPS particles lightweight soil - Tian-shun Hou; Yi-xiang Cui; Xing-ru Pan; Ya-sheng Luo; Qian Liu (Soil Dynamics and Earthquake Engineering, 2023)

Water-in-water emulsions stabilized by self-assembled chitosan colloidal particles - Wanying Cui; Chunmiao Xia; Sheng Xu; Xinke Ye; Yihao Wu; Shukai Cheng; Rongli Zhang; Cuige Zhang; Zongcheng Miao (Carbohydrate Polymers, 2023)

Genetic dissection of additive and epistatic quantitative trait loci controlling pod number per plant in peanut (Arachis hypogaea L.) - Shengzhong Zhang; Xiaohui Hu; Feifei Wang; Huarong Miao; Ye Chu; Weiqiang Yang; Fenggao Cui; Sheng Xu; Jintao Guo; Haoliang Yu; Kefu Zhou; Jing Chen (Euphytica, 2023)

Hepatoprotective Effects of Taurine Against Cadmium-Induced Liver Injury in Female Mice - Jiaming Zheng; Guobin Qiu; Yewen Zhou; Kezhe Ma; Sheng Cui (Biological Trace Element Research, 2023)

Chronic Hemorrhagic Anemia Caused by Hookworm Infection: A Case Report - Baisheng Li; Shihong Chen; Xiangming Cui; Ming Dai; Wenying Meng; Qiong Wu; Huiming Sheng (Acta Parasitologica, 2023)

Bioconversion of corn fiber to bioethanol: Status and perspectives - Minghui Wang; Jie Qiao; Yijie Sheng; Junnan Wei; Haiyang Cui; Xiujuan Li; Guojun Yue (Waste Management, 2023)

Experimental investigation on the mechanical and damping properties of rubber-sand-concrete prepared with recycled waste tires for aseismic isolation layer - Xiancheng Mei; Qian Sheng; Zhen Cui; Maochu Zhang; Daniel Dias (Soil Dynamics and Earthquake Engineering, 2023)

A strategy to promote the ORR electrocatalytic activity by the novel engineering bunched three-dimensional Pd-Cu alloy aerogel - Xiaodong Wu; Chunsheng Ni; Jianwei Man; Xiaodong Shen; Sheng Cui; Xiangbao Chen (Chemical Engineering Journal, 2023)

Experimental and numerical study on the mechanical properties of the rock-concrete contact surface for consideration of ground–liner interaction in rock tunnelling - Maochu Zhang; Qian Sheng; Zhen Cui (European Journal of Environmental and Civil Engineering, 2023)

Deformation mechanism and reinforcement design for the flexural toppled slope of Miaowei HPP - Zhen Cui; Ping-zhi Chen; Wei-jiang Chu; Yong Zhou; Ning Liu; Qian Sheng (Bulletin of Engineering Geology and the Environment, 2023)

Light-enhanced transparent hydrogel for uric acid and glucose detection by four different analytical platforms - Wei Mao; Xingwei Cai; Ruirong Pan; Sheng Tang; Fu Yang; Yanjuan Cui; Jun Sun; Wei Shen (Analytica Chimica Acta, 2023)

A Unified Deterioration Model for Elastic Modulus of Rocks with Coupling Influence of Plastic Shear Strain and Confining Stress - Lan Cui; Qian Sheng; Junjie Zheng; Mingxing Xie; Yang Liu (Rock Mechanics and Rock Engineering, 2022)

Coastline extraction based on multi-scale segmentation and multi-level inheritance classification - Sheng Hui; Guo Mengliang; Gan Yuliang; Xu Mingming; Liu Shanwei; Muhammad Yasir; Cui Jianyong; Wan Jianhua (Frontiers in Marine Science, 2022)
Detailed management of the coastline is critical to the development of coastal states. However, the current classification of the coastline is relatively weak. This study proposed an automatic method to detect coastlines with category attributes based on multi-scale segmentation and multi-level inheritance classification. Fully integrating the advantages of multi-scale segmentation and multi-level classification, it solved the problems that traditional methods could not solve, such as extracting coastlines with categorical attributes, cultivation ponds that are easily affected by tidal flats, and complex coastal terrain. The Chinese GF-2 satellite images are used to extract various types of coastlines in Jiaozhou Bay and its surrounding areas such as the harbor-wharf coastline, silt coastline, pond coastline, rocky coastline, and sandy coastline. Compared with the human interpretation, it is found that the coastline extracted by our proposed method is different by 10.104 km in the harbor-wharf coastline, 0.099 km in the silt coastline, 2.677 km in the pond coastline, 8.831 km in the rocky coastline, and 0.218 km in the sandy coastline. Furthermore, compared to the object-based region growing integrating edge detection (OBRGIE) method, it is increased by 13.52%, 2.16%, 14.48%, 52.57%, and 22.97%, respectively. The results show that our proposed method is algorithmically more reasonable, accurate, and powerful. It can provide data support for refined coastline management.

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Development and Validation of a Diagnostic Nomogram to Predict the Anthracycline-Induced Early Cardiotoxicity in Children with Hematological Tumors - Zhi-yuan Liu; Yun-gong Wang; Xiao-bi Huang; Xiao-hui Qi; Cui-ping Qian; Sheng Zhao (Cardiovascular Toxicology, 2022)
This study aimed to establish and validate an effective nomogram to predict the risk of cardiotoxicity in children after each anthracycline treatment. According to the inclusion and exclusion criteria, the eligible children were randomly divided into the training cohort (75%) and the validation cohort (25%). Least absolute shrinkage and selection operator (LASSO) regression was used to select the predictors and a nomogram was developed. Then, concordance index ( C -index), the area under the curve (AUC), Hosmer–Lemeshow (H–L) test, and decision curve analysis (DCA) were employed to evaluate the performance and clinical utility of nomogram. Internal validation was processed to inspect the stability of the model. A total of 796 eligible children were included in this study and divided into a training set ( n = 597) and a validation set ( n = 199). LASSO regression analysis revealed that cumulative anthracycline dose, ejection fractions, NT-proBNP, and diastolic dysfunction were effective predictors of cardiotoxicity. The nomogram was established based on these variables. The C -index and the AUC of the predicting nomogram were 0.818 in the training cohort and 0.773 in the validation cohort, suggesting that the nomogram had good discrimination. The calibration curve of the nomogram presented no significant deviation from the reference line, and the P -value of the H–L test was 0.283, implying a preferable degree of calibration. The threshold of DCA also reflects that the nomogram is clinically useful. A nomogram was developed to predict anthracycline chemotherapy-induced cardiotoxicity in children with hematological tumors. The nomogram has a good prediction effect and can provide a reference for clinicians’ diagnosis and treatment.

Stable isotopes of water as a tracer for revealing spatial and temporal characteristics of groundwater recharge surrounding Qinghai Lake, China - Dong-sheng Li; Bu-li Cui; Yun-duo Zhao; Feng-lin Zuo (Journal of Mountain Science, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Analytical modelling of the mechanical damage of soil induced by lightning strikes capturing electro-thermal, thermo-osmotic, and electro-osmotic effects - Ping-ping Rao; Pei-hao Ouyang; Sanjay Nimbalkar; Qing-sheng Chen; Zhi-lin Wu; Ji-fei Cui (Journal of Mountain Science, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Stable Isotopes Reveal Water Vapor Sources of Precipitation over the Jiaolai Plain, Shandong Peninsula, China - Ying Wang; Bu-li Cui; Dong-sheng Li; Ya-xuan Wang; Wan-xin Yu; He-hua Zong (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Two-stage analysis of interaction between strain-softening rock mass and liner for circular tunnels considering delayed installation of liner - Lan Cui; Qian Sheng; You-kou Dong; Chen-xi Miao; Jue-hao Huang; Aijun Zhang (European Journal of Environmental and Civil Engineering, 2022)

The load transfer mechanism in reinforced piled embankment under cyclic loading and unloading - Yan Zhuang; Xiaoyan Cui; Sheng Zhang; Guoliang Dai; Xueliang Zhao (European Journal of Environmental and Civil Engineering, 2022)

Deciphering non-steady landscape evolution by in-situ cosmogenic nuclide depth profile - Ye Yang; Lifeng Cui; Sheng Xu; Zhenping Cao; Shuncheng Zhang; Congqiang Liu (Science China Earth Sciences, 2022)

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Mechanical Behavior of the Rock-Concrete Interface for a Bridge Anchorage Structure Using Discrete Element Method - Zhen Cui; Maochu Zhang; Qian Sheng (Journal of Marine Science and Engineering, 2022)
Traditionally, the numerical simulation work of a bridge gravity anchorage structure is performed with a continuous method, such as the finite element method (FEM). However, since the rock mass and gravity anchorage structure are assumed to be continuous in the FEM, the interaction between the rock mass foundation and the concrete of the anchorage is not frequently considered. This paper aims to investigate the problem of the interaction between the rock mass foundation and the concrete of the anchorage. The discrete element method (DEM), which has been verified to be suitable for the modelling of contact problems of discrete blocks, is introduced in this paper to simulate the mechanical behavior of the rock-concrete system of the gravity anchorage structure and its rock mass foundation. Based on the in-situ scale model test for a bridge, the mechanical behavior of the rock-concrete interface was discussed with the DEM method. With the calibrated DEM model, the displacement of the foundation rock mass, contact stresses, and yield state on the rock-concrete interface were numerically investigated. The anti-sliding effect of the keyway and the step at the bottom of the gravity anchorage structure was analyzed. The results show that the anchorage deformation under the design conditions is basically characterized by the rigid rotation around the keyway of platform #2, and that such rotation subsequently affects the anti-shear capacity of the entire gravity anchorage to a large extent. The anchorage scale model could remain stable under the design lateral load such that the rock-concrete interface would remain intact and sufficient shear resistance could be provided by the keyway and steps.

Erosions on the southern Tibetan Plateau: Evidence from in-situ cosmogenic nuclides 10Be and 26Al in fluvial sediments - Xiaolong Zhang; Sheng Xu; Lifeng Cui; Maoliang Zhang; Zhiqi Zhao; Congqiang Liu (Journal of Geographical Sciences, 2022)

Investigating the Deformation and Failure Mechanism of a Submarine Tunnel with Flexible Joints Subjected to Strike-Slip Faults - Guangxin Zhou; Qian Sheng; Zhen Cui; Tianqiang Wang; Yalina Ma (Journal of Marine Science and Engineering, 2021)
Knowledge from historical earthquake events indicates that a submarine tunnel crossing active strike-slip faults is prone to be damaged in an earthquake. Previous studies have demonstrated that the flexible joints are an effective measure for a submarine tunnel crossing a strike-slip fault. The background project of this paper is the second submarine tunnel of Jiaozhou bay. In this work, model tests and numerical simulations are conducted to investigate the deformation and failure mechanism of a submarine tunnel with flexible joints under a strike-slip fault dislocation. The influence of strike-slip faults on a tunnel with flexible joints has been investigated by examining the deformation of rock mass surface, analyzing lining stains, and crack propagation from model tests. Numerical simulations are conducted to study the effects of the design parameters of a tunnel with flexible joints on the mechanical response of the lining. The results showed that the ‘articulated design’ measure can improve the ability of the tunnel to resist the strike-slip faults. In terms of the mechanism of design parameters of a tunnel with flexible joints, this paper finds that increasing the lining thickness, decreasing the lining segment length, and decreasing the tunnel diameter to a reasonable extent could effectively improve the performance of this faulting resistance measure for a tunnel under the strike-slip fault zone dislocation. Compared with the horseshoe tunnel cross-section, the circular tunnel cross-section can improve the ability of the faulting resistance of a tunnel with flexible joints, while the optimal angle of the tunnel crossing the fault zone is 90º. It is concluded that the wider fault zone, smaller flexible joint width, and less stiffness of the flexible joint could make lining safer under a strike-slip fault dislocation. The above research results can serve as a necessary theoretical reference and technical support for the design of reinforcement measures for a submarine tunnel with flexible joints under strike-slip fault dislocation.

Tacrolimus Decreases Cognitive Function by Impairing Hippocampal Synaptic Balance: a Possible Role of Klotho - Yoo Jin Shin; Sun Woo Lim; Sheng Cui; Eun Jeong Ko; Byung Ha Chung; Hong Lim Kim; Tae Ryong Riew; Mun Yong Lee; Chul Woo Yang (Molecular Neurobiology, 2021)

MicroRNA-7a inhibits Isl1 expression to regulate insulin secretion by targeting Raf1 and Mapkap1 in NIT-1 cells - Hui Liu; Di Zhang; Yewen Zhou; Sheng Cui (In Vitro Cellular & Developmental Biology - Animal, 2021)

A New Direct Shear Apparatus for Rock Joints Specialized in Cyclic Loading - Zhen Cui; Qian Sheng; Mao-chu Zhang; Jun-feng Cao; Xian-cheng Mei; Qing-zi Luo (Rock Mechanics and Rock Engineering, 2021)

Cyclin-dependent kinase inhibitor 1B acts as a novel molecule to mediate testosterone synthesis and secretion in mouse Leydig cells by luteinizing hormone (LH) signaling pathway - Hongzhou Guo; Xuan Luo; Longjie Sun; Jianhua Li; Sheng Cui (In Vitro Cellular & Developmental Biology - Animal, 2021)

Seismic signal characteristics and interpretation of the 2020 “6.17” Danba landslide dam failure hazard chain process - Yan Yan; Yifei Cui; Dingzhu Liu; Hui Tang; Yongjian Li; Xin Tian; Lei Zhang; Sheng Hu (Landslides, 2021)

Brucellosis screening and follow-up of seropositive asymptomatic subjects among household members of shepherds in China - Jing Hu; Xiangyi Zhang; Huixin Yang; Siwen Zhang; Taijun Wang; Shuqi An; Mujinyan Li; Fande Li; Jingjing Luo; Fangfang Hu; Dali Wang; Shaonan Ni; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Experimental study on adsorption promotion and desorption restrain of gas-containing coal in low-temperature environment - Fakai Wang; Xuelong Li; Bo Cui; Jian Hao; Xin Gao; Kun Long; Peng Chen; Sheng Wang (Arabian Journal of Geosciences, 2021)

An Experimental Investigation of the Influence of Loading Rate on Rock Tensile Strength and Split Fracture Surface Morphology - Zhen Cui; Sheng Qian; Guimin Zhang; Zhang Maochu (Rock Mechanics and Rock Engineering, 2021)

MiR-375 potentially enhances GnRH expression by targeting Sp1 in GT1-7 cells - Hongjiao Li; Xin Li; Di Zhang; Juxue Li; Sheng Cui (In Vitro Cellular & Developmental Biology - Animal, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Dynamic process analysis of the Niumiangou landslide triggered by the Wenchuan earthquake using the finite difference method and a modified discontinuous deformation analysis - Da Huang; Qiu-jie Meng; Yi-xiang Song; Sheng-hua Cui; Duo-feng Cen (Journal of Mountain Science, 2021)

Isolation, purification and structural characterization of two pectin‐type polysaccharides from Coreopsis tinctoria Nutt. and their proliferation activities on RAW264.7 cells - Si-Liang Jiang; Yi-Xuan Li; Yong-Sheng Cui; Caixia Dong; Juan Du (Glycoconjugate Journal, 2021)

An efficient parallel computing strategy for the processing of large GNSS network datasets - Yang Cui; Zhengsheng Chen; Linyang Li; Qinghua Zhang; Sheng Luo; Zhiping Lu (GPS Solutions, 2021)

A modified rock mass classification considering seismic effects in the basic quality (BQ) system - Zhen Cui; Qian Sheng; Gui-min Zhang; Hua Liu (Bulletin of Engineering Geology and the Environment, 2021)

Effects of Selenium on Arsenic-Induced Liver Lesions in Broilers - Zhihua Ren; Huidan Deng; Youtian Deng; Wenjiao Tang; Qiang Wu; Zhicai Zuo; Hengmin Cui; Yanchun Hu; Shumin Yu; Sheng-yu Xu; Junliang Deng (Biological Trace Element Research, 2021)

Detection and genetic characteristics of porcine bocavirus in central China - Lan-Lan Zheng; Jian-Tao Cui; Han Qiao; Xin-Sheng Li; Xiao-Kang Li; Hong-Ying Chen (Archives of Virology, 2021)

Comparative proteomic study on fem-1b in female and male gonads in Hyriopsis cumingii - Ya-Yu Wang; Sheng-Hua Duan; Sai-Sai Dong; Xiao-Yu Cui; Gui-Ling Wang; Jia-Le Li (Aquaculture International, 2021)

Rhizobium inoculation alleviates separate and combined toxicities of Na+ and Cl– in alfalfa - Lichao Sheng; Guangjuan Cui; Ming Luo; Jiandong Sheng; Xiurong Wang (Acta Physiologiae Plantarum, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

Long non-coding RNA CRNDE promotes malignant progression of hepatocellular carcinoma through the miR-33a-5p/CDK6 axis - Chao Lin; Yien Xiang; Jiyao Sheng; Shui Liu; Mengying Cui; Xuewen Zhang (Journal of Physiology and Biochemistry, 2020)

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

Analytical solution to the 3D tide-induced Lagrangian residual current in a narrow bay with vertically varying eddy viscosity coefficient - Yang Chen; Yanxing Cui; Xiaoxuan Sheng; Wensheng Jiang; Shizuo Feng (Ocean Dynamics, 2020)

Correction to: Pro-arrhythmogenic Effects of the V141M KCNQ1 Mutation in Short QT Syndrome and Its Potential Therapeutic Targets: Insights from Modeling - Hsiang-Chun Lee; Yoram Rudy; Hongwu Liang; Chih-Chieh Chen; Ching-Hsing Luo; Sheng-Hsiung Sheu; Jianmin Cui (Journal of Medical and Biological Engineering, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Seismic signal recognition and interpretation of the 2019 “7.23” Shuicheng landslide by seismogram stations - Yan Yan; Yifei Cui; Xin Tian; Sheng Hu; Jian Guo; Ziang Wang; Shuyao Yin; Liufeng Liao (Landslides, 2020)

Late Pleistocene environmental information on the Diexi paleo-dammed lake of the upper Minjiang River in the eastern margin of the Tibetan Plateau, China - Lan-sheng Wang; Xiao-qun Wang; Jun-hui Shen; Guan Yin; Jie Cui; Xiang-ning Xu; Zhi-long Zhang; Tao Wan; Li-wang Wen (Journal of Mountain Science, 2020)

Experimental Study on Unconsolidated Undrained Shear Strength Characteristics of Synthetic Cotton Fiber Reinforced Soil - Jian-long Liu; Tian-shun Hou; Ya-sheng Luo; Yi-xiang Cui (Geotechnical and Geological Engineering, 2020)

Study on the Dynamic Constitutive Relationship of EPS Particles Light Weight Soil Based on Hardin–Drnevich Model - Tian-shun Hou; Zhen-wei Pei; Ya-sheng Luo; Yi-xiang Cui (Geotechnical and Geological Engineering, 2020)

Safety, pharmacokinetic and pharmacodynamic properties of single ascending dose and continuous infusion of remimazolam besylate in healthy Chinese volunteers - Xiao-yan Sheng; Yan Liang; Xue-yuan Yang; Li-e Li; Xia Ye; Xia Zhao; Yi-min Cui (European Journal of Clinical Pharmacology, 2020)

Structural characteristics of humic substances in buried ancient paddy soils as revealed by 13C NMR spectroscopy - Pei Liu; Weijun Zhou; Haojie Cui; Jie Tan; Sheng Cao (Environmental Geochemistry and Health, 2019)

Estimation of the Mechanical Properties of Igneous Rocks in Consideration of Seismic Effects - Zhen Cui; Qian Sheng; Xianlun Leng; Zeqi Zhu; Yonghui Zhang (Rock Mechanics and Rock Engineering, 2019)

Effect of the drag coefficient on a typhoon wave model - Zhifeng Wang; Yijie Gong; Junnan Cui; Sheng Dong; Kejian Wu (Journal of Oceanology and Limnology, 2019)

microRNA-7 inhibition protects human osteoblasts from dexamethasone via activation of epidermal growth factor receptor signaling - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Sheng-yu Cui; Zhi-ming Cui; Jian-ning Zhao (Molecular and Cellular Biochemistry, 2019)

Terretonin D1, a new meroterpenoid from marine-derived Aspergillus terreus ML-44 - Chang-Jing Wu; Xiang Cui; Biao Xiong; Ming-Sheng Yang; Yun-Xia Zhang; Xiao-Meng Liu (Natural Product Research, 2019)

Influence of Tacrolimus on Depressive-Like Behavior in Diabetic Rats Through Brain-Derived Neurotrophic Factor Regulation in the Hippocampus - Yoo Jin Shin; Yeon Tae Chun; Sun Woo Lim; Kang Luo; Yi Quan; Sheng Cui; Eun Jeong Ko; Byung Ha Chung; Jiyeong Lee; Seongno Hong; Mun Yong Lee; Hee Gyoo Kang; et al. (Neurotoxicity Research, 2019)

Glacier extent changes and possible causes in the Hala Lake Basin of Qinghai-Tibet Plateau - Dong-Sheng Li; Bu-Li Cui; Ying Wang; Bei Xiao; Bao-Fu Jiang (Journal of Mountain Science, 2019)

Prediction of Gas Permeability of Multilayer Woven Reinforcements for SiCf/SiC Porous Composites - Shengjie Yu; Zhaofeng Chen; Yang Wang; Ruiying Luo; Sheng Cui (Transport in Porous Media, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Digital terrain analysis of a landslide on the loess tableland using high-resolution topography data - Sheng Hu; Haijun Qiu; Yanqian Pei; Yifei Cui; Wanli Xie; Xingang Wang; Dongdong Yang; Xiang Tu; Qiang Zou; Puyuan Cao; Mingming Cao (Landslides, 2019)

Investigation of the long-term strength of Jinping marble rocks with experimental and numerical approaches - Zhen Cui; Qian Sheng; Xianlun Leng; Yalina Ma (Bulletin of Engineering Geology and the Environment, 2019)

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Cosmogenic nuclides (10Be and 26Al) erosion rate constraints in the Badain Jaran Desert, northwest China: implications for surface erosion mechanisms and landform evolution - Tong Zhao; Wenjing Liu; Zhifang Xu; Taoze Liu; Sheng Xu; Lifeng Cui; Chao Shi (Geosciences Journal, 2019)

Three new sesquiterpenes from Ainsliaea glabra - Ya-Ping Chen; Cui Tong; Wen-Quan Lu; Yun-Heng Shen; Zhi-Jun Wu; Wan-Sheng Chen (Natural Product Research, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Developing empirical relationships to predict loess slide travel distances: a case study on the Loess Plateau in China - Haijun Qiu; Peng Cui; Sheng Hu; Amar Deep Regmi; Xingang Wang; Dongdong Yang (Bulletin of Engineering Geology and the Environment, 2018)

Landslide distribution and size versus relative relief (Shaanxi Province, China) - Haijun Qiu; Peng Cui; Amar Deep Regmi; Sheng Hu; Yuzhu Zhang; Yi He (Bulletin of Engineering Geology and the Environment, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

On the initiation, movement and deposition of a large landslide in Maoxian County, China - Xiang-jun Pei; Bin Guo; Sheng-hua Cui; Dong-po Wang; Qiang Xu; Tian-tao Li (Journal of Mountain Science, 2018)

Loss of smooth muscle myosin heavy chain results in the bladder and stomach developing lesion during foetal development in mice - Meijuan Li; Shili Li; Yu Rao; Sheng Cui; Kemian Gou (Journal of Genetics, 2018)

Seismogenic fault and topography control on the spatial patterns of landslides triggered by the 2017 Jiuzhaigou earthquake - Chun-hao Wu; Peng Cui; Yu-sheng Li; Irasema Alcántara Ayala; Chao Huang; Shu-jian Yi (Journal of Mountain Science, 2018)

Effects of a controlling geological discontinuity on the seismic stability of an underground cavern subjected to near-fault ground motions - Zhen Cui; Qian Sheng; Xianlun Leng (Bulletin of Engineering Geology and the Environment, 2018)

Centrifuge model test of an irrigation-induced loess landslide in the Heifangtai loess platform, Northwest China - Sheng-hua Cui; Xiang-jun Pei; Hao-yu Wu; Run-qiu Huang (Journal of Mountain Science, 2018)

Cytotoxicity of novel fluorinated alternatives to long-chain perfluoroalkyl substances to human liver cell line and their binding capacity to human liver fatty acid binding protein - Nan Sheng; Ruina Cui; Jinghua Wang; Yong Guo; Jianshe Wang; Jiayin Dai (Archives of Toxicology, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Human biomonitoring of eight trace elements in urine of residents living in rural areas along the Yangtze River, China - Yanjie Cui; Qi Zhong; Mingjun Hu; Jie Sheng; Yuanyuan Yang; Ling Liang; Xiaodong Wang; Yuwei Yang; Mengmeng Zhou; Fen Huang (Environmental Science and Pollution Research, 2017)

Analysis of the Seismic Performance of a Rock Joint with a Modified Continuously Yielding Model - Zhen Cui; Qian Sheng; Xianlun Leng; Yalina Ma (Rock Mechanics and Rock Engineering, 2017)

Pro-arrhythmogenic Effects of the V141M KCNQ1 Mutation in Short QT Syndrome and Its Potential Therapeutic Targets: Insights from Modeling - Hsiang-Chun Lee; Yoram Rudy; Hongwu Liang; Chih-Chieh Chen; Ching-Hsing Luo; Sheng-Hsiung Sheu; Jianmin Cui (Journal of Medical and Biological Engineering, 2017)
Gain-of-function mutations in the pore-forming subunit of I Ks channels, KCNQ1, lead to short QT syndrome (SQTS) and lethal arrhythmias. However, how mutant I Ks channels cause SQTS and the possibility of I Ks -specific pharmacological treatment remain unclear. V141M KCNQ1 is a SQTS associated mutation. We studied its effect on I Ks gating properties and changes in the action potentials (AP) of human ventricular myocytes. Xenopus oocytes were used to study the gating mechanisms of expressed V141M KCNQ1/KCNE1 channels. Computational models were used to simulate human APs in endocardial, mid-myocardial, and epicardial ventricular myocytes with and without β-adrenergic stimulation. V141M KCNQ1 caused a gain-of-function in I Ks characterized by increased current density, faster activation, and slower deactivation leading to I Ks accumulation. V141M KCNQ1 also caused a leftward shift of the conductance-voltage curve compared to wild type (WT) I Ks (V 1/2 = 33.6 ± 4.0 mV for WT, and 24.0 ± 1.3 mV for heterozygous V141M). A Markov model of heterozygous V141M mutant I Ks was developed and incorporated into the O’Hara–Rudy model. Compared to the WT, AP simulations demonstrated marked rate-dependent shortening of AP duration (APD) for V141M, predicting a SQTS phenotype. Transmural electrical heterogeneity was enhanced in heterozygous V141M AP simulations, especially under β-adrenergic stimulation. Computational simulations identified specific I K1 blockade as a beneficial pharmacologic target for reducing the transmural APD heterogeneity associated with V141M KCNQ1 mutation. V141M KCNQ1 mutation shortens ventricular APs and enhances transmural APD heterogeneity under β-adrenergic stimulation. Computational simulations identified I K1 blockers as a potential antiarrhythmic drug of choice for SQTS.

Methane enhances aluminum resistance in alfalfa seedlings by reducing aluminum accumulation and reestablishing redox homeostasis - Weiti Cui; Hong Cao; Ping Yao; Jincheng Pan; Quan Gu; Sheng Xu; Ren Wang; Zhaozeng Ouyang; Qingya Wang; Wenbiao Shen (BioMetals, 2017)

Toxicity comparison of different active fractions extracted from radix Sophorae tonkinensis in zebrafish - Hong-cui Liu; Xiao-yu Zhu; Jiang-hua Chen; Sheng-ya Guo; Chun-qi Li; Zhong-ping Deng (Journal of Zhejiang University-SCIENCE B, 2017)

Behavior of rare earth elements in granitic profiles, eastern Tibetan Plateau, China - Lifeng Cui; Zhiqi Zhao; Congqiang Liu; Sheng Xu; Taoze Liu; Chenglong Tu; Hu Ding (Acta Geochimica, 2017)

Arsenic sorption by red mud-modified biochar produced from rice straw - Chuan Wu; Liu Huang; Sheng-Guo Xue; Yu-Ying Huang; William Hartley; Meng-qian Cui; Ming-Hung Wong (Environmental Science and Pollution Research, 2017)

Effects of endogenous hormones on variation of shoot branching in a variety of non-heading Chinese cabbage and related gene expression - Xue-Wei Cao; Hong-Mi Cui; Yuan Yao; Ai-Sheng Xiong; Xi-Lin Hou; Ying Li (Journal of Plant Biology, 2017)

Rolling motion behavior of rockfall on gentle slope: an experimental approach - Sheng-hua Cui; Xiang-jun Pei; Run-qiu Huang (Journal of Mountain Science, 2017)

Slope aspect effects of loess slides and its spatial differentiation in different geomorphologic types - Haijun Qiu; Amar Deep Regmi; Peng Cui; Sheng Hu; Yanmin Wang; Yi He (Arabian Journal of Geosciences, 2017)

Hydrogen enhances adaptation of rice seedlings to cold stress via the reestablishment of redox homeostasis mediated by miRNA expression - Sheng Xu; Yilong Jiang; Weiti Cui; Qijiang Jin; Yihua Zhang; Duo Bu; Jiangyan Fu; Ren Wang; Feng Zhou; Wenbiao Shen (Plant and Soil, 2017)

Nitrogen removal and microbial community shift in an aerobic denitrification reactor bioaugmented with a Pseudomonas strain for coal-based ethylene glycol industry wastewater treatment - Cong Du; Chong-Wei Cui; Shan Qiu; Sheng-Nan Shi; Ang Li; Fang Ma (Environmental Science and Pollution Research, 2017)

Analysis of S Wave Propagation Through a Nonlinear Joint with the Continuously Yielding Model - Zhen Cui; Qian Sheng; Xianlun Leng (Rock Mechanics and Rock Engineering, 2017)

Chemical constituents and their bioactivities from the fruits of Vitex negundo var. cannabifolia - Sheng-Tao Fang; Na-Na Kong; Bing-Fei Yan; Cui-Yun Yang; Jian-Hua Wang; Su-Jing Liu; Hai-Zhu Jin; Chuan-Hai Xia (Natural Product Research, 2016)

The accumulation and health risk of heavy metals in vegetables around a zinc smelter in northeastern China - Bo Li; Yanhong Wang; Yong Jiang; Guochen Li; Jiehua Cui; Ying Wang; Hong Zhang; Shicheng Wang; Sheng Xu; Ruzhen Wang (Environmental Science and Pollution Research, 2016)

Visualization analysis of CRISPR/Cas9 gene editing technology studies - Quan-sheng Du; Jie Cui; Chun-jie Zhang; Ke He (Journal of Zhejiang University-SCIENCE B, 2016)

Inhibition of biofilm in Bacillus amyloliquefaciens Q-426 by diketopiperazines - Jian-Hua Wang; Cui-Yun Yang; Sheng-Tao Fang; Jian Lu; Chun-Shan Quan (World Journal of Microbiology and Biotechnology, 2016)

The distribution of deep source rocks in the GS Sag: joint MT–gravity modeling and constrained inversion - Yan-Ling Shi; Zu-Zhi Hu; Wen-Hui Huang; Qiang Wei; Sheng Zhang; Cui-Xian Meng; Lian-Sheng Ji (Applied Geophysics, 2016)

New zircon U-Pb ages of the pre-Sturtian rift successions from the western Yangtze Block, South China and their geological significance - Zhuo-Fei Jiang; Xiao-Zhuang Cui; Xin-Sheng Jiang; Jian Wang; Jie-Wen Zhuo; Guo-Qing Xiong; Jun-Ze Lu; Hao Wu; Ya-Nan Wei (International Geology Review, 2016)

Polypore diversity in North America with an annotated checklist - Li-Wei Zhou; Karen K. Nakasone; Harold H. Burdsall; James Ginns; Josef Vlasák; Otto Miettinen; Viacheslav Spirin; Tuomo Niemelä; Hai-Sheng Yuan; Shuang-Hui He; Bao-Kai Cui; Jia-Hui Xing; et al. (Mycological Progress, 2016)

Control Effect of a Large Geological Discontinuity on the Seismic Response and Stability of Underground Rock Caverns: A Case Study of the Baihetan #1 Surge Chamber - Zhen Cui; Qian Sheng; Xianlun Leng (Rock Mechanics and Rock Engineering, 2016)

New method for prediction of shale gas content in continental shale formation using well logs - Sheng-Jie Li; Zhe Cui; Zhen-Xue Jiang; Yu Shao; Wei Liao; Li Li (Applied Geophysics, 2016)

Transgenic NfFeSOD Sedum alfredii plants exhibited profound growth impairments and better relative tolerance to long-term abiotic stresses - Xiang Gao; Wen-Li Ai; Huan Gong; Li-Juan Cui; Bo-Xia Chen; Hong-Yi Luo; Zhong-Chun Zhang; Bao-Sheng Qiu (Plant Biotechnology Reports, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Effects of trawl selectivity and genetic parameters on fish body length under long-term trawling - Yang Yu; Peng Sun; He Cui; Huaxiang Sheng; Fenfang Zhao; Yanli Tang; Zelin Chen (Journal of Ocean University of China, 2015)

Four genetic variants interact to confer susceptibility to atopic dermatitis in Chinese Han population - Changbing Shen; Longdan Liu; Zengqiong Jiang; Xiaodong Zheng; Li Meng; Xianyong Yin; Jing Gao; Yujun Sheng; Jingping Gao; Yang Li; Fusheng Zhou; Fengli Xiao; et al. (Molecular Genetics and Genomics, 2015)

Dynamics of the worldwide number of fungi with emphasis on fungal diversity in China - Yu-Cheng Dai; Bao-Kai Cui; Jing Si; Shuang-Hui He; Kevin D. Hyde; Hai-Sheng Yuan; Xiao-Yong Liu; Li-Wei Zhou (Mycological Progress, 2015)

Potential of utilizing jellyfish as food in culturing Pampus argenteus juveniles - Chun-sheng Liu; Si-qing Chen; Zhi-meng Zhuang; Jing-ping Yan; Chang-lin Liu; He-tong Cui (Hydrobiologia, 2015)

Gene flow from glufosinate-resistant transgenic hybrid rice Xiang 125S/Bar68-1 to weedy rice and cultivated rice under different experimental designs - Guanghui Sun; Weimin Dai; Rongrong Cui; Sheng Qiang; Xiaoling Song (Euphytica, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Arenimonas taoyuanensis sp. nov., a novel bacterium isolated from rice-field soil in China - Shi-Ying Zhang; Wei Xiao; Yun-Sheng Xia; Yong-Xia Wang; Xiao-Long Cui; Nai-Ming Zhang (Antonie van Leeuwenhoek, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Auto-pick first breaks with complex raypaths for undulate surface conditions - Sheng-Pei An; Tian-Yue Hu; Yong-Fu Cui; Wen-Sheng Duan; Geng-Xin Peng (Applied Geophysics, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Flammeopellis bambusicola gen. et. sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and phylogenetic analysis - Chang-Lin Zhao; Xin-Sheng He; Kun-Yuan Wanghe; Bao-Kai Cui; Yu-Cheng Dai (Mycological Progress, 2014)

Flavonoids from the halophyte Apocynum venetum and their antifouling activities against marine biofilm-derived bacteria - Na-Na Kong; Sheng-Tao Fang; Ying Liu; Jian-Hua Wang; Cui-Yun Yang; Chuan-Hai Xia (Natural Product Research, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Ranging behavior of eastern hoolock gibbon (Hoolock leuconedys) in a northern montane forest in Gaoligongshan, Yunnan, China - Dao Zhang; Han-Lan Fei; Sheng-Dong Yuan; Wen-Mo Sun; Qing-Yong Ni; Liang-Wei Cui; Peng-Fei Fan (Primates, 2014)

Coal-burning endemic fluorosis is associated with reduced activity in antioxidative enzymes and Cu/Zn-SOD gene expression - Qi Wang; Kang-ping Cui; Yuan-yuan Xu; Yan-ling Gao; Jing Zhao; Da-sheng Li; Xiao-lei Li; Hou-jin Huang (Environmental Geochemistry and Health, 2014)

Continental flood basalts of the Huashan Group, northern margin of the Yangtze block – implications for the breakup of Rodinia - Qi Deng; Jian Wang; Zheng-Jiang Wang; Xuan-Ce Wang; Yan-Sheng Qiu; Qing-Xiong Yang; Qiu-Ding Du; Xiao-Zhuang Cui; Xiao-Lin Zhou (International Geology Review, 2013)

Genomic sequence analysis of a new reassortant infectious bursal disease virus from commercial broiler flocks in central China - Pei Cui; Shi-Jie Ma; Yu-Geng Zhang; Xin-Sheng Li; Xiao-Yun Gao; Bao-An Cui; Hong-Ying Chen (Archives of Virology, 2013)

Probiotic Bacillus amyloliquefaciens mediate M1 macrophage polarization in mouse bone marrow-derived macrophages - Jian Ji; Sheng-Lan Hu; Zhi-Wen Cui; Wei-Fen Li (Archives of Microbiology, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

RNAi knockdown of rice SE5 gene is sensitive to the herbicide methyl viologen by the down-regulation of antioxidant defense - Sheng Xu; Lijuan Wang; Bo Zhang; Bin Han; Yanjie Xie; Jie Yang; Weigong Zhong; Huiping Chen; Ren Wang; Ning Wang; Weiti Cui; Wenbiao Shen (Plant Molecular Biology, 2012)

Cell-specific distributions of estrogen receptor alpha (ERα) and androgen receptor (AR) in anterior pituitary glands from adult cockerels as revealed by immunohistochemistry - Dehao Sun; Tongtong Cui; Haoshu Luo; Ruiguo Li; Sheng Cui; Jiali Liu (Cell and Tissue Research, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Bt rice expressing Cry1Ab does not stimulate an outbreak of its non-target herbivore, Nilaparvata lugens - Yang Chen; Jun-Ce Tian; Wei Wang; Qi Fang; Zunnu Raen Akhtar; Yu-Fa Peng; Hu Cui; Yu-Yuan Guo; Qi-Sheng Song; Gong-Yin Ye (Transgenic Research, 2012)

Hydrogen sulfide enhances alfalfa (Medicago sativa) tolerance against salinity during seed germination by nitric oxide pathway - Yanqin Wang; Le Li; Weiti Cui; Sheng Xu; Wenbiao Shen; Ren Wang (Plant and Soil, 2012)

A meta-analysis on the association between three promoter variants of TNF-α and Crohn’s disease - Cui Xie; Xiao Feng Liu; Mao Sheng Yang (Molecular Biology Reports, 2012)

Association between Type 2 Diabetes and CDKN2A/B: a meta-analysis study - Xiao Yun Bao; Cui Xie; Mao Sheng Yang (Molecular Biology Reports, 2012)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Characterizing wetland change at landscape scale in Jiangsu Province, China - Chi Xu; Sheng Sheng; Wen Zhou; Lijuan Cui; Maosong Liu (Environmental Monitoring and Assessment, 2011)

Phylogenetic Analysis of Methanogens in the Pig Feces - Sheng-Yong Mao; Cui-Feng Yang; Wei-Yun Zhu (Current Microbiology, 2011)

Isolation and characterization of polymorphic microsatellite markers for the ariake icefish (Salanx ariakensis kishinouye) - Juan Hu; Sheng-Jie Ren; Cui-Zhang Fu; Xiao-Ling Gong (Conservation Genetics Resources, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Proteomic analysis reveals significant elevation of heat shock protein 70 in patients with chronic heart failure due to arrhythmogenic right ventricular cardiomyopathy - Ying-Jie Wei; Yin-Xia Huang; Ya Shen; Chuan-Jue Cui; Xiao-Ling Zhang; Hao Zhang; Sheng-Shou Hu (Molecular and Cellular Biochemistry, 2009)

Trichaptum (Basidiomycota, Hymenochaetales) from China with a description of three new species - Yu-Cheng Dai; Bao-Kai Cui; Hai-Sheng Yuan (Mycological Progress, 2009)

ASYMMETRIC LEAVES2-LIKE38 gene, a Member of AS2/LOB family of Arabidopsis, causes leaf dorsoventral alternation in transgenic cockscomb plants - Lai-Sheng Meng; Hai-Liang Liu; Xianghuan Cui; Xu-Dong Sun; Jian Zhu (Acta Physiologiae Plantarum, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Cytogenetic studies on microsporogenesis and male gametophyte development in autotriploid cucumber (Cucumis sativus L.): implication for fertility and production of trisomics - Wei-Ping Diao; Sheng-You Bao; Biao Jiang; Li Cui; Chun-Tao Qian; Jin-Feng Chen (Plant Systematics and Evolution, 2009)

A novel fibrinolytic enzyme from Cordyceps militaris, a Chinese traditional medicinal mushroom - Li Cui; Ming Sheng Dong; Xiao Hong Chen; Mei Jiang; Xin Lv; Guijun Yan (World Journal of Microbiology and Biotechnology, 2008)

Ontogeny of estrogen receptor alpha, estrogen receptor beta and androgen receptor, and their co-localization with Islet-1 in the dorsal root ganglia of sheep fetuses during gestation - Haoshu Luo; Jiali Liu; Duo Kang; Sheng Cui (Histochemistry and Cell Biology, 2008)

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China - Jian-Fei Chen; Dong-Bo Sun; Cheng-Bao Wang; Hong-Yan Shi; Xiao-Chen Cui; Sheng-Wang Liu; Hua-Ji Qiu; Li Feng (Virus Genes, 2008)

Synthesis and Luminescent Properties of Lanthanide Complexes with a Novel Multipodal Ligand - Zhen-Zhong Yan; Yu Tang; Wei-Sheng Liu; Hai-Xia Cui; Min-Yu Tan (Journal of Fluorescence, 2008)

Expression of androgen receptor and its co-localization with estrogen receptor-alpha in the developing pituitary gland of sheep fetus - XueJun Yuan; YuQin He; JiaLi Liu; HaoShu Luo; JinHua Zhang; Sheng Cui (Histochemistry and Cell Biology, 2007)

Detection and estrogen regulation of leptin receptor expression in rat dorsal root ganglion - Hong Ping Chen; Jingjing Fan; Sheng Cui (Histochemistry and Cell Biology, 2006)

Expression of cysteine sulfinate decarboxylase (CSD) in male reproductive organs of mice - Jian Hua Li; Ya Qin Ling; Jing Jing Fan; Xiao Ping Zhang; Sheng Cui (Histochemistry and Cell Biology, 2006)

Developmental changes of Islet-1 and its co-localization with pituitary hormones in the pituitary gland of chick embryo by immunohistochemistry - Jiali Liu; Yuqin He; Xiumei Wang; Xing Zheng; Sheng Cui (Cell and Tissue Research, 2005)

Ontogeny of estrogen receptor (ER) alpha and its co-localization with pituitary hormones in the pituitary gland of chick embryos - Jiali Liu; Sheng Cui (Cell and Tissue Research, 2005)

Improvement of sandy soil with water-conserving membrane and its effect on crop growth - Xiu-jun Li; Xiang-hao Cui; Qu-sheng Li (Chinese Geographical Science, 2005)

Microbial Metabolism of Quinoline by Comamonas sp. - Mingchao Cui; Fanzhong Chen; Jiamo Fu; Guoying Sheng; Guoping Sun (World Journal of Microbiology and Biotechnology, 2004)

Characterization of protoplasts prepared from the edible fungus, Stropharia rugoso-annulata - Pei-Sheng Yan; Jia-Hui Jiang; Wen-Shan Cui (World Journal of Microbiology and Biotechnology, 2004)

The Nerve Supply to the Orbit of the Bactrian Camel - Sheng Cui; Jianlin Wang; Zheng Ming Xie (Veterinary Research Communications, 2004)

The Nervous Supply to the Nasal Cavity of the Bactrian Camel (Camelus Bactrianus) - Sheng Cui; Jian Hong Wang; Zheng Ming Xie (Veterinary Research Communications, 2004)

Biodegradability of Di(2-Ethylhexyl) Phthalate by Pseudomonas Fluorescens FS1 - Zeng Feng; Cui Kunyan; Fu Jiamo; Sheng Guoying; Yang Huifang (Water, Air, & Soil Pollution, 2002)

Expression of estrogen receptors in the efferent ductule of male sheep fetuses during gestation - Xinggui Tian; Sheng Cui; Jiali Liu; Shaoli Yi (Histochemistry and Cell Biology, 2000)

The Arterial Supply of the Carpal Joint in the Bactrian Camel (Camelus Bactrianus) - Jian-Lin Wang; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

The Arterial Supply of the Cubital Joint in the Bactrian Camel (Camelus bactrianus) - Jian-Lin Wang; Gao-Lan; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

The gross anatomy of the cranial cervical ganglion and its branches in the bactrian camel (Camelus bactrianus) - Cui Sheng; Wang Jian-Ling; Xie Zhen-Ming (Veterinary Research Communications, 1998)